Hollow particles, resin composition, resin molded body, sealing resin composition, cured product, and semiconductor device
By controlling the pH and conductivity in the aqueous dispersion of hollow particles, reducing the content of metals and surfactants, and using suspension polymerization to manufacture hollow particles, the increase in dielectric loss tangent and performance of hollow particles in high-humidity environments are solved. The problem of reduced stability is achieved by reducing the dielectric loss tangent and improving performance stability.
Patent Information
- Application Number
- CN202380040578.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-26
- Filing Date
- 2023-05-24
- Publication Date
- 2025-01-17
AI Technical Summary
In high humidity environments, existing hollow particles tend to increase the tangent of dielectric loss and reduce the performance stability, especially in circuit substrates, which are prone to ion migration.
By controlling the pH in the aqueous dispersion of hollow particles to be above 6.5 and below 7.5, the conductivity is below 50 μS/cm, reducing the content of metals and surfactants, and using suspension polymerization to manufacture hollow particles, ensuring that the porosity is above 50%. The content of cross-linking monomer units is more than 60%.
It significantly reduces the dielectric loss tangent of hollow particles, improves performance stability in high-humidity environments, and prevents ion migration.
Smart Images

Figure CN119156702A9_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to hollow particles, a resin composition and a resin molded body containing the hollow particles, and a sealing resin composition containing the hollow particles, a cured product thereof, and a semiconductor device including the cured product as a sealing material. Background Art
[0002] Hollow particles (hollow resin particles) have cavities inside the particles, so they are added to resins, coatings, or various molded bodies for the purpose of lightening, heat insulation, and low dielectric constant. Their uses cover a wide range of fields such as automobiles, bicycles, aviation, electrical, electronics, construction, home appliances, containers, stationery, tools, and shoes.
[0003] In the fields of electrical and electronic fields, attempts have been made to add hollow particles to insulating materials in order to reduce the dielectric constant and dielectric loss tangent of insulating materials.
[0004] For example, Patent Document 1 discloses hollow cross-linked resin particles as low dielectric constant hollow cross-linked resin particles that can be used in organic insulating materials. The hollow cross-linked resin particles are obtained by polymerizing 1 to 100% by weight of a cross-linking monomer and 0 to 99% by weight of a non-cross-linking monomer (here, the total of the cross-linking monomer and the non-cross-linking monomer is set to 100% by weight), and the average particle size is 0.03 to 10 μm, and the average metal ion concentration present in the particles is 50 ppm or less. The hollow cross-linked resin particles of Patent Document 1 are manufactured by dispersing the monomers in water using an emulsifier (surfactant) and performing seed polymerization.
[0005] Patent document 2 discloses a kind of microparticle-attached hollow particles, which are obtained by heating and expanding heat-expandable microspheres and attaching microparticles such as inorganic microparticles to the outer surface thereof, wherein the heat-expandable microspheres are composed of an outer shell and a foaming agent contained in the outer shell, the ash content is less than 1.2% by weight, and the outer shell is formed by a specific thermoplastic resin.
[0006] Patent document 3 discloses hollow particles obtained by dispersing an organic mixed solution containing an aromatic crosslinking monomer (a), an aromatic monofunctional monomer (b), a (meth)acrylate monomer (c) having a specific structure, a side chain crystalline polyolefin, a polymerization initiator, and an organic solvent in an aqueous solution containing a surfactant and subjecting the mixture to suspension polymerization.
[0007] Patent document 4 discloses a hollow particle obtained by dispersing an oil phase containing a hydrocarbon monomer having a crosslinking monomer content of 70% by mass or more, a hydrocarbon solvent having 5 to 8 carbon atoms, and a polymerization initiator in an aqueous phase and subjecting the resulting particle to suspension polymerization, wherein the aqueous phase is a metal hydroxide colloid that is poorly soluble in water.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2000-313818;
[0011] Patent Document 2: Japanese Patent Application Publication No. 2015-3951;
[0012] Patent document 3: International Publication No. 2021 / 085189;
[0013] Patent document 4: International Publication No. 2022 / 092076. Summary of the invention
[0014] Problem that the invention aims to solve
[0015] The hollow particles added for the purpose of lowering the dielectric loss tangent of various materials preferably have a lower dielectric loss tangent.
[0016] In addition, the circuit substrate is also required to have stable performance in a high humidity environment, for example, it is required that ion migration (a phenomenon in which ionized metal moves between electrodes and causes a short circuit) and other failures do not occur in a high humidity environment. However, in a circuit substrate containing hollow particles, ion migration is sometimes prone to occur in a high humidity environment.
[0017] An object of the present invention is to provide hollow particles having a reduced dielectric loss tangent and improved performance stability in a high-humidity environment.
[0018] Furthermore, an object of the present invention is to provide a resin composition and a resin molded article which contain the hollow particles to reduce the dielectric loss tangent and suppress the reduction in performance stability under a high-humidity environment.
[0019] Furthermore, the present invention particularly aims to provide a sealing resin composition and a cured product thereof as the above-mentioned resin composition and resin molded body, and further to provide a semiconductor device including the cured product of the sealing resin composition as a sealing material.
[0020] Solutions for solving problems
[0021] The present inventors have found that a metal or a surfactant contained in hollow particles so as to be easily soluble in water tends to increase the dielectric loss tangent of the hollow particles and reduce the performance stability under a high-humidity environment, thereby completing the present invention.
[0022] The present invention provides hollow particles having a shell containing a resin and a hollow part surrounded by the shell, wherein the porosity is 50% or more, the shell containing a polymer as the resin, wherein the content of crosslinkable monomer units in 100% by mass of all monomer units of the polymer is 60% by mass or more,
[0023] When the volume is 0.35cm 3 In an aqueous dispersion of hollow particles obtained by dispersing the hollow particles of in 100 mL of ion-exchanged water, the pH is 6.5 to 7.5, and the electrical conductivity is 50 μS / cm or less.
[0024] In the hollow particles of the present invention, it is preferred that the content of the hydrocarbon monomer units exceeds 50% by mass in 100% by mass of all monomer units of the polymer.
[0025] In the hollow particles of the present invention, the metal content is preferably 700 ppm or less.
[0026] In the hollow particles of the present invention, the content of the surfactant present on the surface of the hollow particles is preferably 200 ppm or less.
[0027] In the hollow particles of the present invention, it is preferred that the dielectric loss tangent at a frequency of 10 GHz is 1.00×10 -3 the following.
[0028] In the hollow particles of the present invention, it is preferred that the relative dielectric constant at a frequency of 10 GHz is 1.00 or more and 1.40 or less.
[0029] In the hollow particles of the present invention, the porosity is preferably 70% or more.
[0030] Furthermore, the present invention provides a resin composition comprising the hollow particles of the present invention and a matrix resin.
[0031] Furthermore, the present invention provides a resin molded article obtained from the resin composition of the present invention.
[0032] Furthermore, the present invention provides a sealing resin composition comprising the hollow particles of the present invention and an epoxy resin.
[0033] Furthermore, the present invention provides a cured product of the sealing resin composition of the present invention.
[0034] Furthermore, the present invention provides a semiconductor device comprising a cured product of the sealing resin composition of the present invention as a sealing material.
[0035] Effects of the Invention
[0036] As described above, the present invention provides hollow particles having a reduced dielectric loss tangent and improved performance stability under a high-humidity environment.
[0037] Furthermore, the present invention provides a resin composition and a resin molded article, which contain the hollow particles and thereby have a reduced dielectric loss tangent and suppress a decrease in performance stability under a high-humidity environment.
[0038] Furthermore, the present invention particularly provides a sealing resin composition and a cured product thereof as the above-mentioned resin composition and resin molded body, and further provides a semiconductor device including the cured product of the sealing resin composition as a sealing material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a diagram for explaining an example of the method for producing hollow particles of the present invention. DETAILED DESCRIPTION
[0040] The hollow particles of the present invention have a shell containing a resin and a hollow part surrounded by the shell, and are characterized in that the porosity is 50% or more, the shell contains a polymer as the resin, and the content of crosslinking monomer units in 100% by mass of all monomer units of the polymer is 60% by mass or more,
[0041] When the volume is 0.35cm 3 In an aqueous dispersion of hollow particles obtained by dispersing the hollow particles of in 100 mL of ion-exchanged water, the pH is 6.5 to 7.5, and the electrical conductivity is 50 μS / cm or less.
[0042] The hollow particles of the present invention are hollow particles in which the content of metal and surfactant contained in the hollow particles in a manner that is easily soluble in water is sufficiently small so that the increase in the dielectric loss tangent of the hollow particles caused by the metal or surfactant and the decrease in the performance stability of the hollow particles under a high humidity environment are suppressed. The hollow particles of the present invention are sufficiently small in amount of both metal and surfactant, so that compared with the case where only the amount of one is reduced, the effect of reducing the dielectric loss tangent and the effect of improving the performance stability under a high humidity environment are significantly excellent. The hollow particles of the present invention are highly effective in suppressing the occurrence of ion migration in a circuit substrate containing hollow particles by reducing the amount of ionic surfactants on the particle surface in particular among surfactants.
[0043] In an aqueous dispersion in which hollow particles are dispersed in ion exchange water, there is a tendency for the conductivity to increase as the amount of metal or ionic surfactant dissolved from the hollow particles increases, there is a tendency for the pH to increase as the amount of metal dissolved from the hollow particles increases, and there is a tendency for the pH to become alkaline (greater than 7.5) when the amount of ionic surfactant reaches a certain value or more.
[0044] The inventors have found that there is a tendency that the more the amount of metal and ionic surfactant dissolved from the hollow particles into the aqueous dispersion, the more the dielectric loss tangent of the hollow particles rises, and the performance stability of the hollow particles under a high humidity environment is more likely to deteriorate, especially in a circuit substrate containing hollow particles, ion migration is more likely to occur. Dielectric loss tangent is "the degree to which a part of its energy becomes heat and is lost when an electric field is applied". It is speculated that the metal and ionic surfactant dissolved from the hollow particles into the aqueous dispersion are attached to the particle surface in a state that is easily freed from the hollow particles, and are attached to the particle surface when the particles are in a dry state. It is speculated that by attaching metal to the particle surface, polarization is generated when an electric field is applied, and therefore, the dielectric loss tangent of the hollow particles becomes high. In addition, it is speculated that it is attached to the particle surface by a surfactant, so that it becomes easy to adsorb moisture in the air, therefore, the dielectric loss tangent of the hollow particles is increased.
[0045] In addition, in a circuit substrate in which hollow particles are contained in an insulating resin layer, it is presumed that when a metal or a surfactant is attached to the surface of the hollow particles, the metal or the surfactant absorbs moisture and becomes easily ionized in a high humidity environment, thereby easily generating dendrites, and thus ion migration is likely to occur. In particular, when an ionic surfactant among surfactants is attached to the surface of the hollow particles, a large amount of ion components are contained, which further promotes the ionization of the metal, and thus ion migration is more likely to occur.
[0046] It is speculated that in the hollow particles of the present invention, by setting the pH in the aqueous dispersion of the hollow particles to be greater than 6.5 and less than 7.5 and the electrical conductivity to less than 50 μS / cm, the amount of metal and ionic surfactant contained in the hollow particles is reduced in a manner that is particularly likely to affect the dielectric loss tangent of the hollow particles and the performance stability in a high-humidity environment.
[0047] From the aspect that hollow particles can be made simply and impurities attached to the surface can be easily removed and then can be easily controlled to the desired particle size, the hollow particles of the present invention are usually made by suspension polymerization. In the suspension polymerization of the polymerizable monomers using the crosslinking monomers more than 60% by mass, by being dispersed in the droplets of the monomer composition in the suspension, the components constituting the shell and the hydrophobic solvent are easily phase separated, and a shell with excellent strength is formed, so that the deformation of the particles can be suppressed, and therefore, a hollow part clearly distinguished from the shell can be formed. The hollow particles of the present invention are made by using a large amount of suspension polymerization of the polymerizable monomers containing crosslinking monomers like this, and therefore, become the following particles: in all monomer units of 100% by mass of the polymer constituting the shell, the content of the crosslinking monomer unit is more than 60% by mass, with a hollow part clearly distinguished from the shell. In addition, by forming a shell with excellent strength, the deformation of the particles can be suppressed, and the porosity can be fully increased to more than 50%, so that a low dielectric loss tangent can be achieved. In addition, the dielectric loss tangent of the air layer is 0, and the larger the proportion of the air layer in the hollow particle is, the lower the dielectric loss tangent is. Therefore, the higher the porosity of the hollow particle is, the lower the dielectric loss tangent can be achieved.
[0048] In addition, in the hollow particles prepared by the suspension polymerization method, by using an inorganic dispersion stabilizer as a dispersion stabilizer instead of a surfactant as a dispersion stabilizer, it is possible to obtain hollow particles that do not contain a surfactant. However, when an inorganic dispersion stabilizer is used as a dispersion stabilizer, metals that can be dissolved into water are easily retained on the surface of the obtained hollow particles. In order to fully reduce the amount of metal remaining on the surface of the particles, the pH in the aqueous dispersion of the above-mentioned hollow particles is made to be above 6.5 and below 7.5, and the conductivity is made to be below 50 μS / cm. For example, when manufacturing hollow particles, it is preferred that the polymerization temperature is set to 80°C or above in the polymerization process, and the preferred method described later is adopted in the cleaning process.
[0049] In the present invention, the aqueous dispersion of hollow particles for measuring pH and conductivity may further contain a dispersant as long as the conductivity is 2 μS / cm or less in a state without hollow particles. The type and content of the dispersant can be appropriately adjusted so that the hollow particles are uniformly dispersed. The aqueous dispersion of hollow particles for measuring pH and conductivity is a state in which no powder exists on the upper part and all the powder is dispersed in water when observed with the naked eye.
[0050] As the dispersant that can be used in the aqueous dispersion of hollow particles for measuring pH and conductivity, a dispersant that does not change the pH and conductivity of ion-exchanged water when added to ion-exchanged water can be appropriately selected and used. For example, a nonionic surfactant can be used.
[0051] As the nonionic surfactant, it can be appropriately selected from known nonionic surfactants and used, and there is no particular limitation, and examples thereof include: polyoxyalkylene nonionic surfactants such as higher alcohol alkylene oxide adducts, alkylphenol alkylene oxide adducts, fatty acid alkylene oxide adducts, higher alkylamine alkylene oxide adducts, polyhydric alcohol aliphatic ester alkylene oxide adducts, polypropylene glycol ethylene oxide adducts, fatty acid amide alkylene oxide adducts, polyoxyalkylene styrenated phenyl ethers, etc.; polyol nonionic surfactants such as polyethylene oxide, fatty acid esters of glycerol, alkyl glycosides, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol or sorbitan, sucrose fatty acid esters, alkyl ethers of polyhydric alcohols, and aliphatic amides of alkanolamines; nonionic polymer compounds having both hydrophilic groups and hydrophobic groups such as polyvinyl alcohol and polyvinyl pyrrolidone, etc. In particular, polyoxyalkylene nonionic surfactants can be preferably used.
[0052] The concentration of the nonionic surfactant in the aqueous dispersion of the hollow particles is not particularly limited, and can be, for example, 0.05% by mass to 1% by mass.
[0053] In addition, in the present invention, the hollow particles added to the aqueous dispersion for measuring pH and conductivity are hollow particles immediately before use. Here, the hollow particles immediately before use refer to, for example, hollow particles used in a mixture with other materials, and are hollow particles immediately before being mixed with other materials. In the case of hollow particles used alone as a coating material, etc., they are hollow particles immediately before being used for their purpose. In addition, in the case of measuring the above-mentioned pH and conductivity for hollow particles manufactured in the state of a dispersion, the same method as the solvent removal step in the method for manufacturing hollow particles described later is used to obtain dried hollow particles whose hollow parts are filled with gas from the dispersion, and a volume of 0.35 cm 3 The dried hollow particles were dispersed in 100 mL of ion-exchanged water to obtain an aqueous dispersion, and the pH and conductivity of the aqueous dispersion were measured.
[0054] In the present invention, the volume is 0.35 cm 3 The hollow particles are obtained by measuring the weight (g) of the hollow particles obtained by the following formula (1). In the following formula (1), the apparent density D1 of the hollow particles is the same as the apparent density D1 of the hollow particles measured when calculating the porosity described later.
[0055] .
[0056] The pH of the aqueous dispersion of the hollow particles may be 6.5 or more and 7.5 or less. From the perspective of reducing the dielectric loss tangent of the hollow particles and improving the performance stability of the hollow particles in a high-humidity environment, the pH is preferably 6.8 or more and 7.3 or less, and more preferably 6.9 or more and 7.2 or less.
[0057] The conductivity of the aqueous dispersion of the hollow particles can be 50 μS / cm or less. From the perspective of reducing the dielectric loss tangent of the hollow particles and improving the performance stability of the hollow particles in a high humidity environment, it is preferably 40 μS / cm or less, more preferably 30 μS / cm or less, and further preferably 20 μS / cm or less. The lower limit of the conductivity is not particularly limited, and for example, it may be 5 μS / cm or more, or 10 μS / cm or more.
[0058] Hereinafter, an example of a method for producing the hollow particles of the present invention will be described, and then the hollow particles of the present invention will be described in further detail.
[0059] In addition, in the present invention, "to" in a numerical range means that the numerical values described before and after it are included as the lower limit and the upper limit.
[0060] 1. Method for manufacturing hollow particles
[0061] As a method for producing the hollow particles of the present invention, there can be mentioned, for example, a method having the following steps:
[0062] A step of preparing a mixed solution comprising a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer, and an aqueous medium;
[0063] A step of suspending the mixed liquid to prepare a suspension in which droplets of a monomer composition containing the polymerizable monomer, the hydrophobic solvent, and the polymerization initiator are dispersed in the aqueous medium;
[0064] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion surrounded by a shell containing a resin and containing the hydrophobic solvent in the hollow portion; and
[0065] A step of washing the precursor particles.
[0066] The above-mentioned manufacturing method follows the following basic technology: by suspending a mixed liquid containing a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer and an aqueous medium, a suspension is prepared in which droplets having a distribution structure in which the polymerizable monomer and the hydrophobic solvent are phase-separated, the polymerizable monomer is concentrated on the surface side, and the hydrophobic solvent is concentrated in the center are dispersed in the aqueous medium; by supplying the suspension to a polymerization reaction, the surface of the droplets is solidified to form hollow particles having a hollow part filled with the hydrophobic solvent.
[0067] In the present invention, hollow particles whose hollow parts are filled with a hydrophobic solvent may be considered as intermediates of hollow particles whose hollow parts are filled with a gas and may be referred to as “precursor particles.” In the present invention, a “precursor composition” refers to a composition containing precursor particles.
[0068] The above-mentioned manufacturing method includes the steps of preparing a mixed solution, preparing a suspension, supplying the suspension to a polymerization reaction, and washing the precursor particles, and may further include steps other than these. In addition, as long as it is technically feasible, two or more of the above-mentioned steps and other additional steps may be performed simultaneously as one step, or the order may be reversed. For example, the preparation of the mixed solution and the suspension may be performed simultaneously in one step by adding materials for preparing the mixed solution while suspending the mixed solution.
[0069] As a preferred example of the method for producing hollow particles of the present invention, there can be mentioned a method comprising the following steps.
[0070] (1) Mixed solution preparation process
[0071] A step of preparing a mixed solution comprising a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer, and an aqueous medium;
[0072] (2) Suspension process
[0073] A step of suspending the mixed solution to prepare a suspension in which droplets of a monomer composition containing a polymerizable monomer, a hydrophobic solvent, and a polymerization initiator are dispersed in an aqueous medium;
[0074] (3) Polymerization process
[0075] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion surrounded by a shell containing a resin and containing a hydrophobic solvent in the hollow portion;
[0076] (4) Cleaning process
[0077] A step of washing the precursor particles; and
[0078] (5) Solvent Removal Process
[0079] A step of removing the hydrophobic solvent contained in the precursor particles to obtain hollow particles.
[0080] Figure 1 This is a schematic diagram showing an example of the production method of the present invention. Figure 1 (1) to (5) in the figure correspond to the above-mentioned steps (1) to (5). The white arrows between the figures indicate the order of the steps. Figure 1 The schematic diagrams are only for explanation, and the manufacturing method of the present invention is not limited to the method shown in the figures. In addition, the structure, size and shape of the materials used in the manufacturing method of the present invention are not limited to the structure, size and shape of the various materials in these figures.
[0081] Figure 1 (1) is a cross-sectional schematic diagram showing an embodiment of a mixed solution in the mixed solution preparation process. As shown in the figure, the mixed solution includes an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 refers to a material with low polarity that is not easily mixed with the aqueous medium 1. In the present invention, the low-polarity material 2 includes a polymerizable monomer, a hydrophobic solvent, and a polymerization initiator.
[0082] Figure 1 (2) is a cross-sectional schematic diagram showing an embodiment of the suspension in the suspension process. The suspension includes an aqueous medium 1 and droplets 3 of a monomer composition dispersed in the aqueous medium 1. The droplets 3 of the monomer composition include polymerizable monomers, a hydrophobic solvent, and a polymerization initiator, but the distribution in the droplets is uneven. The droplets 3 of the monomer composition have the following structure: the hydrophobic solvent 4a and the material 4b other than the hydrophobic solvent containing the polymerizable monomer are separated, the hydrophobic solvent 4a is biased in the center, the material 4b other than the hydrophobic solvent is biased on the surface side, and the dispersion stabilizer (not shown) is attached to the surface.
[0083] Figure 1 (3) is a schematic cross-sectional view showing an embodiment of a precursor composition containing precursor particles obtained by a polymerization process, wherein the precursor particles contain a hydrophobic solvent in a hollow portion. The precursor composition comprises an aqueous medium 1 and precursor particles 5 dispersed in the aqueous medium 1, wherein the precursor particles 5 contain a hydrophobic solvent 4a in a hollow portion. The shell 6 forming the outer surface of the precursor particle 5 is formed by polymerization of the polymerizable monomer in the droplets 3 of the monomer composition, and the polymer containing the polymerizable monomer is used as a resin.
[0084] Figure 1 (4) is a schematic cross-sectional view showing one embodiment of the precursor particles in the cleaning step. Figure 1 (4) shows that from the above Figure 1 The precursor particles 5 are separated from the state (3) and re-slurried with ion exchange water 1a.
[0085] Figure 1 (5) is a schematic cross-sectional view showing one embodiment of the hollow particles after the solvent removal step. Figure 1 (5) shows that from the above Figure 1 The state after the ion exchange water 1a and the hydrophobic solvent 4a are removed from the state (4). By removing the hydrophobic solvent contained in the precursor particles, hollow particles 10 having a hollow part 7 filled with gas inside the shell 6 can be obtained.
[0086] Hereinafter, the above five steps and other steps will be described in sequence.
[0087] (1) Mixed solution preparation process
[0088] This step is a step of preparing a mixed solution containing a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer, and an aqueous medium. The mixed solution may further contain other materials within a range that does not impair the effects of the present invention.
[0089] The materials of the mixed solution are described in order: (A) polymerizable monomer, (B) hydrophobic solvent, (C) polymerization initiator, (D) dispersion stabilizer, and (E) aqueous medium.
[0090] (A) Polymerizable Monomer
[0091] In the present invention, the polymerizable monomer refers to a compound having an addition polymerizable functional group (sometimes simply referred to as a polymerizable functional group in the present invention). In the present invention, as the polymerizable monomer, a compound having an ethylenically unsaturated bond as an addition polymerizable functional group is generally used.
[0092] In the present invention, as a polymerizable monomer, a known polymerizable monomer used in the preparation of hollow polymer particles in the past can be used, without particular limitation, and from the aspect of being easy to form a hollow portion in the particle, it is preferred to include at least a crosslinking monomer, and a non-crosslinking monomer can also be further included. When the polymerizable monomer includes a crosslinking monomer, when the suspension is supplied to the polymerization reaction, the crosslinking density of the polymer precipitated on the surface of the droplet becomes high, and then the precipitates are also crosslinked with each other, so the crosslinking density of the shell can be increased. Therefore, it is easy to form a shell with excellent strength, and the hollow particles are easy to become spherical, and a hollow portion clearly distinguished from the shell is easily formed in the particle.
[0093] In the present invention, a polymerizable monomer having only one polymerizable functional group is referred to as a non-crosslinkable monomer, and a polymerizable monomer having two or more polymerizable functional groups is referred to as a crosslinkable monomer. A crosslinkable monomer is a polymerizable monomer that forms a crosslink bond in a resin by a polymerization reaction.
[0094] In addition, in the present invention, a polymerizable monomer composed of carbon and hydrogen is referred to as a hydrocarbon monomer, a crosslinkable monomer composed of carbon and hydrogen is referred to as a crosslinkable hydrocarbon monomer, and a non-crosslinkable monomer composed of carbon and hydrogen is referred to as a non-crosslinkable hydrocarbon monomer. In addition, a polymerizable monomer having a (meth)acryloyl group as a polymerizable functional group is referred to as an acrylic monomer, a crosslinkable monomer having a (meth)acryloyl group as a polymerizable functional group is referred to as a crosslinkable acrylic monomer, and a non-crosslinkable monomer having a (meth)acryloyl group as a polymerizable functional group is referred to as a non-crosslinked acrylic monomer. In the crosslinkable acrylic monomer, at least one polymerizable functional group may be a (meth)acryloyl group, and preferably all polymerizable functional groups are (meth)acryloyl groups.
[0095] In addition, in the present invention, (meth)acrylate represents acrylate and methacrylate, (meth)acrylic acid represents each of acrylic acid and methacrylic acid, and (meth)acryloyl represents each of acryloyl and methacryloyl.
[0096] Examples of the crosslinking monomer include aromatic divinyl monomers such as divinylbenzene, divinylbiphenyl, and divinylnaphthalene; diene monomers such as butadiene, isoprene, 2,3-dimethylbutadiene, pentadiene, and hexadiene; difunctional crosslinking hydrocarbon monomers such as alicyclic olefins such as dicyclopentadiene, cyclopentadiene, and ethylenetetracyclododecene; high molecular weight crosslinking hydrocarbon monomers such as polybutadiene, polyisoprene, block copolymers of styrene and butadiene (SBS), and block copolymers of styrene and isoprene (SIS); allyl (meth)acrylate, vinyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, tricyclodecane dimethanol, and the like. Difunctional cross-linking acrylic monomers such as di(meth)acrylate and 3-(meth)acryloyloxy-2-hydroxypropyl(meth)acrylate; trifunctional or higher cross-linking acrylic monomers such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and ethoxylates thereof; cross-linking allyl monomers such as diallyl phthalate; high molecular weight cross-linking acrylic monomers such as polyphenylene ether modified with (meth)acrylic acid at both ends, high molecular weight cross-linking vinyl monomers such as polyphenylene ether modified with vinyl at both ends, etc. These cross-linking monomers can be used alone or in combination of two or more.
[0097] Examples of the non-crosslinking monomer include aromatic monovinyl monomers such as styrene, vinyltoluene, α-methylstyrene, p-methylstyrene, ethylvinylbenzene, ethylvinylbiphenyl, and ethylvinylnaphthalene; monoolefin monomers such as ethylene, propylene, and butene; and non-crosslinking hydrocarbon monomers such as alicyclic monoolefins such as vinylcyclohexane, norbornene, and tricyclododecene; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tert-butylaminoethyl (meth)acrylate, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-aminoethyl (meth)acrylate, (meth)acrylic acid, (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, Non-crosslinking acrylic monomers such as ethylene glycol (meth)acrylate, propoxy polyethylene glycol (meth)acrylate, butoxy polyethylene glycol (meth)acrylate, hexyl polyethylene glycol (meth)acrylate, octyloxy polyethylene glycol polypropylene glycol (meth)acrylate, lauryl polyethylene glycol (meth)acrylate, stearyloxy polyethylene glycol (meth)acrylate, phenoxy polyethylene glycol polypropylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol propylene glycol mono(meth)acrylate, polyethylene glycol tetramethylene glycol (meth)acrylate, propylene glycol polybutylene glycol mono(meth)acrylate, and monoethylene glycol mono(meth)acrylate; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated aromatic vinyl monomers such as halogenated styrene; halogenated vinyl monomers such as vinyl chloride; vinylidene halide monomers such as vinylidene chloride; vinyl pyridine, etc. In addition to these, high molecular weight non-crosslinking monomers such as polystyrene modified with (meth)acrylic acid at one end and polymethyl methacrylate modified with (meth)acrylic acid at one end can also be used. These non-crosslinking monomers can be used alone or in combination of two or more.
[0098] From the aspect of improving the pressure resistance of hollow particles and the aspect that hollow particles are easy to maintain high porosity, in 100 parts by mass of polymerizable monomers, the content of crosslinkable monomer is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and more preferably 80 parts by mass or more. On the other hand, from the aspect of easily reducing the dielectric loss tangent of hollow particles, in 100 parts by mass of polymerizable monomers, the content of crosslinkable monomer is preferably 96 parts by mass or less, more preferably 90 parts by mass or less, and more preferably 85 parts by mass or less.
[0099] From the aspect that the polymerization reaction is easy to be stable, as the polymerizable monomer, a polymerizable monomer whose polymerizable functional group is (meth) acryloyl or vinyl is preferred. In addition, in the present invention, stable polymerization reaction means that the reactivity of the polymerization reaction is good and the polymerization reaction proceeds uniformly. In the present invention, in 100 parts by mass of the polymerizable monomer, the content of the polymerizable monomer whose polymerizable functional group is (meth) acryloyl or vinyl is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, and further preferably 95 parts by mass or more.
[0100] From the aspect of improving the dielectric properties of the hollow particles, the content of the hydrocarbon monomer in 100 parts by mass of the polymerizable monomer is preferably greater than 50 parts by mass, more preferably 70 parts by mass or more, further preferably 90 parts by mass or more, and further preferably 95 parts by mass or more. The above-mentioned polymerizable monomer can be composed of hydrocarbon monomers. The higher the proportion of hydrocarbon monomers in the polymerizable monomers, the lower the relative dielectric constant and dielectric loss tangent of the hollow particles.
[0101] In addition, in the present invention, the smaller the relative dielectric constant and the dielectric loss tangent are, the better the dielectric properties are.
[0102] From the viewpoint of improving the dielectric properties of the hollow particles and achieving excellent pressure resistance, the hydrocarbon monomer preferably contains at least a crosslinkable hydrocarbon monomer. As the crosslinkable hydrocarbon monomer, an aromatic divinyl monomer is particularly preferred, and divinylbenzene is particularly preferred.
[0103] In addition, from the perspective of particularly improving the dielectric properties of the hollow particles, the hydrocarbon monomer preferably contains a crosslinkable hydrocarbon monomer and a non-crosslinkable hydrocarbon monomer in combination. As the non-crosslinkable hydrocarbon monomer, an aromatic monovinyl monomer is particularly preferred, and at least one selected from ethylvinylbenzene and styrene is more preferred.
[0104] The content of the polymerizable monomer in the mixed solution is not particularly limited, but is preferably 15 to 50% by mass, more preferably 20 to 40% by mass, and further preferably 20 to 30% by mass, relative to 100% by mass of the total mass of the components in the mixed solution excluding the aqueous medium.
[0105] Furthermore, in the obtained hollow particles, the content of the polymerizable monomer is preferably 96% by mass or more, and more preferably 97% by mass or more, relative to 100% by mass of the total mass of the solid components excluding the hydrophobic solvent among the materials forming the oil phase in the mixed liquid, in order to suppress the deterioration of the dielectric properties, the reduction in strength, and the reduction in performance stability under a high-humidity environment.
[0106] In the present invention, the solid content refers to all components except the solvent, and liquid polymerizable monomers and the like are included in the solid content.
[0107] (B) Hydrophobic solvent
[0108] The hydrophobic solvent used in the production method of the present invention is a non-polymerizable organic solvent that is poorly soluble in water.
[0109] The hydrophobic solvent acts as a spacer material for forming a hollow portion inside the particle. In the suspension process described later, a suspension formed by dispersing droplets of a monomer composition containing a hydrophobic solvent in an aqueous medium can be obtained. In the suspension process, phase separation occurs in the droplets of the monomer composition, and as a result, the hydrophobic solvent with low polarity easily gathers inside the droplets of the monomer composition. Finally, in the droplets of the monomer composition, the hydrophobic solvent is distributed inside according to their respective polarities, and other materials except the hydrophobic solvent are distributed around them.
[0110] Then, in the polymerization step described below, an aqueous dispersion containing precursor particles containing the hydrophobic solvent can be obtained. That is, the hydrophobic solvent is accumulated inside the particles, and hollow parts filled with the hydrophobic solvent are formed inside the obtained precursor particles.
[0111] The hydrophobic solvent can be appropriately selected from known hydrophobic solvents without particular limitation, and examples thereof include esters such as ethyl acetate and butyl acetate; ether esters such as propylene glycol monomethyl ether acetate and propylene glycol monoethyl ether acetate; and hydrocarbon solvents. In particular, hydrocarbon solvents can be preferably used.
[0112] Examples of hydrocarbon solvents include aliphatic hydrocarbons including chain hydrocarbon solvents such as pentane, hexane, heptane, octane, 2-methylbutane and 2-methylpentane, paraffin solvents, and cyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane and cycloheptane; and aromatic hydrocarbons such as benzene, toluene and xylene.
[0113] These hydrophobic solvents can be used alone or in combination of two or more.
[0114] In the suspension step, an organic solvent having a lower solubility in water than the crosslinking monomer included in the polymerizable monomer is preferably selected as the hydrophobic solvent from the viewpoint of facilitating phase separation of the polymerizable monomer and the hydrophobic solvent in the droplets of the monomer composition.
[0115] In addition, when the polymerizable monomer contains a hydrocarbon monomer in a ratio greater than 50% by mass, it is preferred to use a chain hydrocarbon solvent as the hydrophobic solvent, more preferably a chain hydrocarbon solvent having 5 to 8 carbon atoms, and further preferably at least one selected from pentane, hexane, heptane and octane.
[0116] In addition, the boiling point of the hydrophobic solvent is not particularly limited. From the viewpoint of easy removal in the solvent removal step described later, it is preferably 130°C or lower, and more preferably 100°C or lower. On the other hand, from the viewpoint of easy inclusion in the precursor particles, it is preferably 50°C or higher, and more preferably 60°C or higher.
[0117] In addition, when the hydrophobic solvent is a mixed solvent containing multiple hydrophobic solvents and has multiple boiling points, it is preferred that the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent is below the above-mentioned upper limit value, and it is preferred that the boiling point of the solvent with the lowest boiling point among the solvents contained in the mixed solvent is above the above-mentioned lower limit value.
[0118] In addition, the hydrophobic solvent used in the production method of the present invention preferably has a relative dielectric constant of 2.5 or less, more preferably 2.0 or less at 20°C. The relative dielectric constant is one of the indicators indicating the polarity of a compound. It is believed that when the relative dielectric constant of the hydrophobic solvent is sufficiently small, preferably 2.5 or less, more preferably 2.0 or less, phase separation in the droplets of the monomer composition proceeds rapidly, and a hollow portion is easily formed.
[0119] Examples of the hydrophobic solvent having a relative dielectric constant of 2.0 or less at 20° C. are as follows. The values in parentheses are relative dielectric constants.
[0120] Pentane (1.8), hexane (1.9), heptane (1.9), octane (1.9), cyclohexane (2.0).
[0121] Regarding the relative dielectric constant at 20° C., reference can be made to the values described in known literature (e.g., Chemical Society of Japan, "Basic Handbook of Chemistry", 4th revised edition, Maruzen Co., Ltd., issued on September 30, 1993, pages II-498 to II-503), and other technical information. As a method for measuring the relative dielectric constant at 20° C., for example, a relative dielectric constant test performed in accordance with 23 of JIS C 2101:1999 with the measuring temperature set to 20° C. can be cited.
[0122] The porosity of the hollow particles can be adjusted by changing the amount of the hydrophobic solvent in the mixed solution. In the suspension step described later, the polymerization reaction is carried out in a state where the oil droplets containing the polymerizable monomers and the like contain the hydrophobic solvent, so there is a tendency that the porosity of the obtained hollow particles becomes higher as the content of the hydrophobic solvent increases.
[0123] In the present invention, from the aspects of easy control of the particle size of the hollow particles, easy improvement of the porosity while maintaining the strength of the hollow particles, and easy reduction of the amount of residual hydrophobic solvent in the particles, it is preferred that the content of the hydrophobic solvent in the mixed solution is 50 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the polymerizable monomer. The content of the hydrophobic solvent in the mixed solution is more preferably 70 parts by mass or more and 300 parts by mass or less, and further preferably 80 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the polymerizable monomer.
[0124] (C) Polymerization initiator
[0125] In the manufacturing method of the present invention, the mixed solution preferably contains an oil-soluble polymerization initiator as a polymerization initiator. The oil-soluble polymerization initiator is not particularly limited as long as it is a lipophilic polymerization initiator with a solubility in water of less than 0.2% by mass, and can include, for example, organic peroxides such as benzoyl peroxide, lauroyl peroxide, peroxy-2-ethylhexanoic acid tert-butyl ester, diethyl peroxy acetate tert-butyl ester, and peroxy pivalate; 2,2'-azobis (2,4-dimethylvaleronitrile), azobisisobutyronitrile, 2,2'-azobis (4-methoxy-2,4-dimethylvaleronitrile) and other azo compounds. From the aspect of easily improving the dielectric properties of hollow particles, it is particularly preferred to use organic peroxides as oil-soluble polymerization initiators.
[0126] The content of the polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and further preferably 1 to 5 parts by mass relative to 100 parts by mass of the polymerizable monomer in the mixed solution. When the content of the polymerization initiator is above the above lower limit, the polymerization reaction can be fully carried out, and when the content of the polymerization initiator is below the above upper limit, the risk of the oil-soluble polymerization initiator remaining after the polymerization reaction is completed is small, and the risk of unexpected side reactions is also small.
[0127] (D) Dispersion stabilizer
[0128] The dispersion stabilizer is an agent that disperses the droplets of the monomer composition in the aqueous medium in the suspension process. Examples of the dispersion stabilizer include inorganic dispersion stabilizers and surfactants. In the present invention, an inorganic dispersion stabilizer is preferably used as the dispersion stabilizer because it is easy to control the particle size of the droplets in the suspension so that the particle size distribution of the obtained hollow particles can be narrowed, and because the shell is prevented from becoming too thin and the strength of the hollow particles is prevented from decreasing.
[0129] Examples of the inorganic dispersion stabilizer include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, and iron hydroxide; and inorganic compounds such as silicon dioxide. These inorganic dispersion stabilizers can be used alone or in combination of two or more.
[0130] As the inorganic dispersion stabilizer, an inorganic dispersion stabilizer that is poorly soluble in water can be preferably used. Here, poorly soluble in water means that the solubility in 100 g of water is preferably 0.5 g or less.
[0131] As the inorganic dispersion stabilizer, metal hydroxides are particularly preferred, and magnesium hydroxide is more preferred.
[0132] In the present invention, it is particularly preferred to use the sparingly water-soluble inorganic dispersion stabilizer in the form of colloidal particles dispersed in an aqueous medium, that is, to use it in the form of a colloidal dispersion containing the sparingly water-soluble inorganic dispersion stabilizer colloidal particles. Thus, the inorganic dispersion stabilizer can be easily removed by the washing step described later, and therefore, it is easy to make the pH in the aqueous dispersion of hollow particles 6.5 or more and 7.5 or less, and the conductivity 50 μS / cm or less.
[0133] The colloidal dispersion containing the sparingly water-soluble inorganic dispersion stabilizer colloidal particles can be prepared, for example, by reacting at least one selected from alkali metal hydroxides and alkaline earth metal hydroxides with a water-soluble polyvalent metal salt (excluding alkaline earth metal hydroxides) in an aqueous medium.
[0134] Examples of the alkali metal hydroxide salt include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. Examples of the alkaline earth metal hydroxide salt include barium hydroxide, calcium hydroxide, etc.
[0135] As the water-soluble polyvalent metal salt, any polyvalent metal salt showing water solubility other than the compounds belonging to the above-mentioned alkaline earth metal hydroxide salts may be used, and examples thereof include magnesium metal salts such as magnesium chloride, magnesium phosphate, and magnesium sulfate; calcium metal salts such as calcium chloride, calcium nitrate, calcium acetate, and calcium sulfate; aluminum metal salts such as aluminum chloride and aluminum sulfate; barium salts such as barium chloride, barium nitrate, and barium acetate; zinc salts such as zinc chloride, zinc nitrate, and zinc acetate, etc. Among these, magnesium metal salts, calcium metal salts, and aluminum metal salts are preferred, magnesium metal salts are more preferred, and magnesium chloride is particularly preferred.
[0136] There is no particular limitation on the method for reacting at least one selected from the above-mentioned alkali metal hydroxides and alkaline earth metal hydroxides with the above-mentioned water-soluble polyvalent metal salt in an aqueous medium. For example, an aqueous solution of at least one selected from the above-mentioned alkali metal hydroxides and alkaline earth metal hydroxides can be mixed with an aqueous solution of a water-soluble polyvalent metal salt.
[0137] Furthermore, colloidal silica can also be used as a colloidal dispersion containing colloid particles of an inorganic dispersion stabilizer that is sparingly soluble in water.
[0138] The content of the dispersion stabilizer is not particularly limited, and is preferably 0.5 to 15 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer and the hydrophobic solvent. When the content of the dispersion stabilizer is above the above lower limit, the droplets of the monomer composition can be fully dispersed in the suspension without being combined. On the other hand, when the content of the dispersion stabilizer is below the above upper limit, the viscosity of the suspension can be prevented from increasing during granulation, thereby avoiding the failure of the suspension to block the granulator.
[0139] The content of the dispersion stabilizer is preferably 0.5 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the aqueous medium.
[0140] Furthermore, in the production of the hollow particles of the present invention, it is preferred not to use a surfactant as a dispersion stabilizer.
[0141] In the present invention, surfactant refers to a compound having both a hydrophilic group and a hydrophobic group in one molecule, including well-known surfactants such as ionic surfactants and nonionic surfactants, and polymer compounds that bring about a dispersing effect such as polyvinyl alcohol, etc., which are generally used as surfactants. The solubility of surfactants in water at 25°C is generally 1 g / L or more.
[0142] Examples of the ionic surfactant include anionic surfactants, cationic surfactants, and amphoteric surfactants.
[0143] Examples of the anionic surfactant include carboxylates such as alkali metal salts of higher fatty acids; sulfate esters such as higher alcohol sulfate esters and higher alkyl ether sulfate esters; sulfonates such as alkylbenzene sulfonates, alkyl sulfonates, and paraffin sulfonates; and phosphates such as higher alcohol phosphate esters.
[0144] Examples of the cationic surfactant include quaternary ammonium salts such as alkyltrimethylammonium salts.
[0145] Examples of the amphoteric surfactant include amino acid-type amphoteric surfactants such as higher alkylaminopropionates, and betaine-type amphoteric surfactants such as higher alkyl dimethyl betaine and higher alkyl dihydroxyethyl betaine.
[0146] Examples of the nonionic surfactant include the same nonionic surfactants as those that can be used in the aqueous dispersion of hollow particles for measuring pH and conductivity.
[0147] In addition, examples of polymer compounds that can be used as surfactants and bring about a dispersing effect include polymer compounds having both a hydrophilic group and a hydrophobic group, such as polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, ethyl cellulose, polyacrylic acid, polyacrylimide, polyethylene oxide, and poly(hydroxystearic acid-g-methyl methacrylate-co-methacrylic acid) copolymer.
[0148] Furthermore, although not particularly limited, the molecular weight of the surfactant is usually less than 3,000.
[0149] (E) Water-based media
[0150] In the present invention, the aqueous medium refers to a medium selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent.
[0151] When a mixture of water and a hydrophilic solvent is used, it is important not to make the polarity of the mixture as a whole too low from the viewpoint of forming droplets of the monomer composition. In this case, for example, the mass ratio of water to the hydrophilic solvent (water:hydrophilic solvent) can be 99:1 to 50:50.
[0152] The hydrophilic solvent in the present invention is not particularly limited as long as it is a solvent that is fully miscible with water without phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol; tetrahydrofuran (THF); and dimethyl sulfoxide (DMSO).
[0153] The content of the aqueous medium is not particularly limited. From the viewpoint of making the particle size and porosity of the hollow particles within the preferred range described below, the lower limit is preferably 200 parts by mass or more, more preferably 400 parts by mass or more, and further preferably 600 parts by mass or more, relative to 100 parts by mass of the polymerizable monomer contained in the mixed solution. The upper limit is preferably 1000 parts by mass or less, and more preferably 800 parts by mass or less.
[0154] The mixed solution may further contain other materials different from the above-mentioned materials (A) to (E) within a range not impairing the effects of the present invention.
[0155] A mixed solution can be obtained by mixing the above-mentioned materials with other materials as needed and stirring them appropriately. In the mixed solution, the oil phase containing the above-mentioned (A) polymerizable monomer, (B) hydrophobic solvent and (C) lipophilic materials such as polymerization initiator is dispersed in a water phase containing (D) dispersion stabilizer and (E) aqueous medium in a particle size of about several mm. Depending on the type of materials, the dispersion state of these materials in the mixed solution can be observed even with the naked eye.
[0156] In the mixed solution preparation step, the mixed solution can be obtained by simply mixing the above-mentioned materials with other materials as needed and stirring appropriately, but from the perspective of making the shell easy to become uniform, it is preferred to separately prepare an oil phase containing a polymerizable monomer, a hydrophobic solvent and a polymerization initiator and an aqueous phase containing a dispersion stabilizer and an aqueous medium in advance, and mix them to prepare the mixed solution. In the present invention, the following colloidal dispersion can be preferably used as the aqueous phase, and the colloidal dispersion is obtained by dispersing a sparingly water-soluble inorganic dispersion stabilizer in the form of colloidal particles in an aqueous medium.
[0157] By preparing the oil phase and the water phase separately in advance and then mixing them, hollow particles having a uniform composition of the shell portion can be produced, and the particle size of the hollow particles can also be easily controlled.
[0158] (2) Suspension process
[0159] The suspension step is a step of suspending the mixed solution to prepare a suspension in which droplets of the monomer composition containing a hydrophobic solvent are dispersed in an aqueous medium.
[0160] The suspension method for forming the droplets of the monomer composition is not particularly limited, and a known suspension method can be used. As a disperser used in preparing the suspension, for example, a horizontal or vertical pipeline disperser such as Milder (: product name) manufactured by Ohira Kiko Co., Ltd., Cavitron (: product name) manufactured by Eurotec Co., Ltd., or a pipeline disperser manufactured by IKA (for example, DISPAX-REACTOR (registered trademark) DRS (: product name)) or an emulsifying disperser such as the Homomixer MARK II series manufactured by Plemix Co., Ltd. can be used.
[0161] In the suspension prepared in the suspension step, droplets of the monomer composition containing the lipophilic material and having a particle size of about 1 to 10 μm are uniformly dispersed in the aqueous medium. Such droplets of the monomer composition are not easily observed with the naked eye, but can be observed using a known observation device such as an optical microscope.
[0162] In the suspension step, phase separation occurs in the droplets of the monomer composition, so the hydrophobic solvent with low polarity tends to gather inside the droplets. As a result, in the obtained droplets, the hydrophobic solvent is distributed inside and the material other than the hydrophobic solvent is distributed around the droplets.
[0163] The droplets of the monomer composition dispersed in the aqueous medium are formed by surrounding the oil-soluble monomer composition with a dispersion stabilizer. The droplets of the monomer composition contain an oil-soluble polymerization initiator, a polymerizable monomer, and a hydrophobic solvent.
[0164] The droplets of the monomer composition are fine oil droplets, and the oil-soluble polymerization initiator generates polymerization initiation radicals inside the fine oil droplets. Therefore, precursor particles having a target particle size can be produced without excessive growth of the fine oil droplets.
[0165] In the suspension polymerization method using such an oil-soluble polymerization initiator, the polymerization initiator has no chance to contact the polymerizable monomer dispersed in the aqueous medium. Therefore, by using an oil-soluble polymerization initiator, it is possible to suppress the generation of excess resin particles such as dense particles with a small particle size other than the target resin particles having a hollow portion as a by-product.
[0166] (3) Polymerization process
[0167] This step is a step of preparing a precursor composition containing precursor particles by subjecting the suspension obtained by the above-mentioned suspension step to a polymerization reaction, wherein the above-mentioned precursor particles have a hollow part surrounded by a shell containing a resin and contain a hydrophobic solvent in the hollow part. The precursor particles are formed by polymerization of polymerizable monomers contained in droplets of the monomer composition, and the shells of the precursor particles contain a polymer of the above-mentioned polymerizable monomers as a resin.
[0168] The polymerization method is not particularly limited, and for example, a batch method, a semi-continuous method, a continuous method, or the like can be adopted.
[0169] The polymerization temperature is not particularly limited, but is usually 40 to 90° C., and is preferably 80° C. or higher from the viewpoint of reducing the amount of residual unreacted polymerizable monomers.
[0170] The polymerization reaction time is usually 1 to 48 hours, and preferably 8 hours or more from the viewpoint of reducing the amount of residual unreacted polymerizable monomers. From the viewpoint of ease of production, the upper limit of the polymerization reaction time is preferably 36 hours or less.
[0171] The polymerization temperature and reaction time are preferably adjusted in such a way that the polymerization conversion of the polymerizable monomer reaches 90% or more. In addition, in the present invention, the polymerization conversion is obtained by the mass of the solid content of the precursor particles obtained by the polymerization reaction and the mass of the polymerizable monomer remaining in an unreacted state after the polymerization reaction by the following formula (2). The mass of the unreacted polymerizable monomer can be measured by gas chromatography (GC) as described later.
[0172] .
[0173] By sufficiently reducing the amount of unreacted polymerizable monomer remaining after the polymerization step, the hollow particles can be inhibited from agglomerating with each other in the precursor composition. This makes it easy to remove the metal and surfactant present on the surface of the precursor particles in the cleaning step described later, so that in the above-mentioned aqueous dispersion of hollow particles, it is easy to obtain hollow particles with a pH of 6.5 to 7.5 and a conductivity of 50 μS / cm or less.
[0174] (4) Cleaning process
[0175] This step is a step of washing the precursor particles obtained in the above-mentioned polymerization step, and may be a step of removing the above-mentioned dispersion stabilizer.
[0176] In the present invention, the volume is 0.35 cm 3 In the aqueous dispersion of hollow particles obtained by dispersing the hollow particles in 100mL of ion exchange water, in order to make the pH above 6.5 and below 7.5 and the conductivity below 50μS / cm, it is preferred to perform the cleaning process by the following method. First, an acid or a base is added to the precursor composition obtained by the polymerization process to dissolve the dispersion stabilizer contained in the precursor particles in the aqueous medium. At this time, in the case of the presence of condensed precursor particles, it is preferred to eliminate the condensation. Then, the precursor particles are separated from the aqueous medium. Next, the separated precursor particles are dispersed in ion exchange water and re-pulped, and then the process of separating the precursor particles is repeated three or more times. In the case where condensed precursor particles exist in the slurry obtained by re-pulping, it is also preferred to de-agglomerate. By performing such a cleaning process, the dispersion stabilizer present on the surface of the precursor particles can be fully removed. In the present invention, the number of times the precursor particles separated after adding acid or alkali are re-pulped and separated is referred to as the "number of cleaning times". The number of cleaning times is as described above, preferably three times or more, more preferably four times or more. The upper limit of the number of washing times is not particularly limited, and from the viewpoint of ease of production, it may be, for example, six times or less, or five times or less.
[0177] When an acid or a base is added to the precursor composition, when the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in an acid, it is preferred to add an acid to the precursor composition. On the other hand, when the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in an alkali, it is preferred to add an alkali to the precursor composition.
[0178] When an inorganic dispersion stabilizer soluble in an acid is used as the dispersion stabilizer, it is preferred to add an acid to the precursor composition and adjust the pH to preferably 6.5 or less, more preferably 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, and sulfuric acid is particularly preferred from the viewpoint of high removal efficiency of the dispersion stabilizer and low burden on production equipment.
[0179] The method for separating the precursor particles from the aqueous medium is not particularly limited, and examples thereof include centrifugal separation, filtration, static separation, etc. Filtration is particularly preferred from the perspective of ease of operation and high removal efficiency of the dispersion stabilizer. In addition, when separating the precursor particles from the aqueous medium, the precursor particles obtained by filtration, etc. are preferably dehydrated by a known method.
[0180] The precursor composition to which an acid or alkali is added, and the slurry obtained by dispersing the separated precursor particles in ion exchange water and re-slurrying is preferably in a state where the precursor particles are not agglomerated with each other. That is, it is preferred that the agglomerates of the precursor particles cannot be observed with the naked eye in the slurry. In order to make the precursor particles in the slurry in a state where there is no agglomeration, an effective method is: for example, in the above-mentioned polymerization step, the polymerization reaction is carried out until the polymerization conversion rate reaches more than 90% to reduce the amount of unreacted polymerizable monomers remaining in the precursor particles; unreacted monomers are removed from the slurry in advance. When the precursor particles agglomerate with each other in the slurry, it is difficult to clean the inside of the agglomerate, and thus, the dispersion stabilizer is likely to remain in the hollow particles. By making the precursor particles not agglomerated with each other in the slurry, it is easy to clean the surface of each particle, and therefore, it is easy to remove the dispersion stabilizer. In addition, since the surface area of the precursor particles in the slurry becomes larger, the filtration speed of the slurry is slowed down, and the cleaning time becomes longer, which also makes the dispersion stabilizer easy to remove.
[0181] (5) Solvent Removal Process
[0182] This step is a step of removing the hydrophobic solvent contained in the precursor particles.
[0183] In the present invention, a method of removing the hydrophobic solvent contained in the precursor particles separated from the slurry by solid-liquid separation in a gas can be adopted, and a method of removing the hydrophobic solvent contained in the precursor particles in a slurry formed by dispersing the precursor particles in an aqueous medium can also be adopted. The former method has the advantage of easily reducing the metal content in the obtained hollow particles, and the latter method has the advantage of reducing the residual amount of the hydrophobic solvent.
[0184] The method of solid-liquid separation is the same as the method of separating precursor particles from the aqueous medium.
[0185] The precursor particles after solid-liquid separation may be pre-dried before removing the hydrophobic solvent. Pre-drying can be performed, for example, by drying the solid content including the precursor particles obtained by solid-liquid separation using a drying device such as a dryer or a drying tool such as a hand dryer.
[0186] In this process, "in gas" strictly refers to an environment in which there is no liquid component outside the precursor particles, and an environment in which there is only a very small amount of liquid component outside the precursor particles that does not affect the removal of the hydrophobic solvent. "In gas" can be said to refer to a state in which the precursor particles are not present in the slurry, and can also be said to refer to a state in which the precursor particles are present in the dry powder. That is, it is important to remove the hydrophobic solvent in an environment in which the precursor particles are directly in contact with the external gas.
[0187] The method for removing the hydrophobic solvent in the precursor particles in the gas is not particularly limited, and a known method can be adopted. Examples of the method include reduced pressure drying, heating drying, air flow drying, and a combination of these methods.
[0188] In particular, when a heat drying method is used, the heating temperature needs to be above the boiling point of the hydrophobic solvent and below the highest temperature at which the shell structure of the precursor particles does not collapse. Therefore, although it depends on the composition of the shell in the precursor particles and the type of the hydrophobic solvent, the heating temperature can be set to 50 to 200°C, 70 to 200°C, or 100 to 200°C, for example.
[0189] By the drying operation in the gas, the hydrophobic solvent inside the precursor particles is replaced by the external gas, and as a result, hollow particles in which the hollow part is occupied by the gas can be obtained.
[0190] The dry atmosphere is not particularly limited and can be appropriately selected according to the purpose of the hollow particles. As the dry atmosphere, for example, air, oxygen, nitrogen, argon, etc. can be considered. In addition, after the inside of the hollow particles is temporarily filled with gas, reduced pressure drying is carried out, thereby, hollow particles with a temporary vacuum inside can also be obtained.
[0191] As a method for removing the hydrophobic solvent contained in the precursor particles in the slurry formed by dispersing the precursor particles in the aqueous medium, for example, a method for distilling and removing the hydrophobic solvent contained in the precursor particles in the slurry under a specified pressure can be cited, and more specifically, a method for distilling and removing the hydrophobic solvent in the precursor particles by introducing an inert gas or water vapor such as nitrogen, argon, helium, etc. into the slurry under a specified pressure selected from high pressure, normal pressure, and reduced pressure can be cited. From the aspect of excellent removal efficiency of the hydrophobic solvent, it is particularly preferred to introduce an inert gas into the slurry formed by dispersing the precursor particles under a specified pressure to distill and remove the hydrophobic solvent in the hollow particles.
[0192] As a method for introducing the inert gas into the slurry, for example, a method of bubbling the inert gas into the slurry can be preferably used.
[0193] In addition, from the perspective of reducing the residual amount of the hydrophobic solvent, the temperature when the inert gas is introduced into the slurry is preferably a temperature above the temperature after subtracting 35°C from the boiling point of the hydrophobic solvent, preferably a temperature above the temperature after subtracting 30°C from the boiling point of the hydrophobic solvent, and more preferably a temperature above the temperature after subtracting 20°C from the boiling point of the hydrophobic solvent. Here, when the above-mentioned hydrophobic solvent is a mixed solvent containing multiple hydrophobic solvents and has multiple boiling points, the boiling point of the hydrophobic solvent in the solvent removal process refers to the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent, that is, the highest boiling point among the multiple boiling points. In addition, the temperature when the inert gas is introduced into the slurry is usually set to a temperature above the polymerization temperature in the above-mentioned polymerization process. The temperature when the inert gas is introduced into the slurry is not particularly limited and can be set to 50 to 100°C.
[0194] The conditions for bubbling the inert gas into the slurry are appropriately adjusted according to the type and amount of the hydrophobic solvent so as to remove the hydrophobic solvent contained in the precursor particles. There are no particular limitations. For example, the inert gas may be bubbled at 1 to 3 L / min for 1 to 72 hours.
[0195] By introducing an inert gas into the slurry, a slurry of hollow particles containing the inert gas can be obtained. The slurry is subjected to solid-liquid separation, and the water remaining in the obtained hollow particles is dried to remove the water, thereby obtaining hollow particles in which the hollow part is occupied by the gas.
[0196] (6) Others
[0197] As a step other than the above-mentioned steps (1) to (5), for example, a step of replacing the interior of the particle may be added.
[0198] The particle internal replacement process refers to the process of replacing the gas or liquid inside the hollow particle with other gas or liquid. By such replacement, the environment inside the hollow particle can be changed, or molecules can be selectively enclosed inside the hollow particle, or the chemical structure inside the hollow particle can be modified according to the application.
[0199] 2. Hollow particles
[0200] The hollow particles of the present invention are particles having a shell (outer shell) containing a resin and a hollow portion surrounded by the shell.
[0201] In the present invention, the hollow part is a cavity-like space clearly distinguished from the shell of the hollow particle formed by the resin material. The shell of the hollow particle may have a porous structure, in which case the hollow part has a size that can be clearly distinguished from a plurality of microscopic spaces uniformly dispersed in the porous structure. From the viewpoint of dielectric properties, the hollow particle of the present invention preferably has a dense shell.
[0202] The hollow part of the hollow particles can be confirmed by, for example, SEM observation of a particle cross section or by directly observing the particles with TEM.
[0203] Furthermore, in order to exhibit excellent dielectric properties, it is preferred that the hollow particles of the present invention have a hollow portion filled with a gas such as air.
[0204] In the hollow particles of the present invention, from the aspect of reducing the dielectric loss tangent of the hollow particles and improving the performance stability of the hollow particles in a high humidity environment, the content of the surfactant present on the particle surface is preferably 200ppm or less, more preferably 100ppm or less, and further preferably 50ppm or less. By not using a surfactant as a dispersion stabilizer in the manufacturing process of the above-mentioned hollow particles, the content of the surfactant present on the surface of the hollow particles can be made less than the detection limit.
[0205] In the present invention, the content of the surfactant present on the surface of the hollow particles refers to the ratio of the mass of the surfactant present on the surface of the hollow particles to the mass of the hollow particles. The surfactant present on the surface of the hollow particles can be extracted by, for example, ultrasonically treating the hollow particles in water. The type and mass of the surfactant extracted into the water can be determined by 1 The peak position and peak intensity of the H-NMR spectrum can be used to determine the amount of surfactant present on the surface of the hollow particles. In this method, the detection limit of the amount of surfactant present on the surface of the hollow particles is usually 0.05 ppm.
[0206] In the hollow particles of the present invention, the content of the metal contained in the hollow particles is preferably 700ppm or less, more preferably 400ppm or less, and further preferably 200ppm or less, from the perspective that the pH in the aqueous dispersion of the hollow particles is easily within the range of 6.5 or more and 7.5 or less, and the conductivity is easily 50μS / cm or less. Here, the content of the metal contained in the hollow particles refers to the ratio of the total mass of the metal components contained in the hollow particles to the mass of the hollow particles. In order to make the content of the metal contained in the hollow particles below the above-mentioned upper limit, it is preferred, for example, to use a polymerization initiator that does not contain a metal, use ion exchange water as an aqueous medium, perform the above-mentioned cleaning process in the manufacture of the hollow particles, and adopt a method of removing the hydrophobic solvent contained in the precursor particles in the gas in the above-mentioned solvent removal process.
[0207] If the pH in the aqueous dispersion of the hollow particles is 6.5 or more and 7.5 or less, and the conductivity is 50 μS / cm or less, the hollow particles of the present invention may also contain metals. The content of the metal contained in the hollow particles of the present invention may be less than the detection limit, or may be 50 ppm or more, or 80 ppm or more, or 100 ppm or more, or 120 ppm or more, or 150 ppm or more.
[0208] The content of metal contained in the hollow particles can be measured by ICP emission analysis. The type of metal can be determined by fluorescent X-ray analysis (XRF). In this method, the detection limit of the content of metal contained in the hollow particles is usually 5 ppm.
[0209] The hollow particles of the present invention include a polymer of the above-mentioned polymerizable monomer as the main component of the shell, and the polymer forms the skeleton of the shell of the hollow particles. In the total solid content of 100% by mass of the shell, the content of the polymer of the above-mentioned polymerizable monomer is preferably 98% by mass or more, more preferably 99% by mass or more, and further preferably 99.5% by mass or more. By making the content of the above-mentioned polymer more than the above-mentioned lower limit, the deterioration of dielectric properties, the reduction of strength and the reduction of performance stability under high humidity environments can be suppressed in the hollow particles.
[0210] Furthermore, from the viewpoint that the pH in the aqueous dispersion of the hollow particles mentioned above is easily within the range of 6.5 to 7.5 and the electrical conductivity is easily 50 μS / cm or less, the content of the polymerizable monomer remaining in an unreacted state in 100% by mass of the total solid content of the shell is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, further preferably 0.8% by mass or less, further preferably 0.5% by mass or less, and particularly preferably 0.15% by mass or less.
[0211] The content of the polymerizable monomer remaining in an unreacted state can be determined, for example, by subjecting a solution obtained by extracting the unreacted polymerizable monomer from the hollow particles to gas chromatography measurement.
[0212] If the content of the polymerizable monomer remaining in an unreacted state is 1.5% by mass or less, the content of each monomer unit contained in the polymer constituting the shell can be calculated from the charged amount of the polymerizable monomer.
[0213] Furthermore, the shell of the hollow particle of the present invention may further contain other materials such as a polymer different from the polymerizable monomer described above, within a range not impairing the effects of the present invention.
[0214] The composition of the polymer contained in the hollow particles of the present invention usually corresponds to the composition of the above-mentioned polymerizable monomers.
[0215] From the aspect of improving the pressure resistance of hollow particles and the aspect that hollow particles are easy to maintain high porosity, among all monomer units of 100% by mass of the above-mentioned polymer, the content of cross-linked monomer unit is preferably more than 60% by mass, more preferably more than 70% by mass, and more preferably more than 80% by mass. When the pressure resistance of hollow particles is good, high porosity can also be maintained after being added to various materials, so it is easy to play the effects such as low dielectric constant and low dielectric loss tangent brought by hollow particles. On the other hand, from the aspect of easily reducing the dielectric loss tangent of hollow particles, the content of cross-linked monomer unit is preferably less than 96% by mass, more preferably less than 90% by mass, and more preferably less than 85% by mass. The content of cross-linked monomer unit is below the above-mentioned upper limit and the combination comprises cross-linked monomer unit and non-cross-linked monomer unit in the shell, and the more non-cross-linked monomer unit is included, the less residual double bonds that do not contribute to the reaction are, so the less components that carry out molecular motion when an electric field is applied. It is therefore inferred that the energy loss is reduced and, thereby, the dielectric loss tangent of the hollow particles is reduced.
[0216] From the aspect of improving the dielectric properties of hollow particles, the content of hydrocarbon monomer units in 100% by mass of all monomer units of the above-mentioned polymer is preferably greater than 50% by mass, more preferably more than 70% by mass, further preferably more than 90% by mass, and more preferably more than 95% by mass. The above-mentioned polymer can be composed of hydrocarbon monomer units. The higher the proportion of hydrocarbon monomer units in the above-mentioned polymer, the smaller the relative dielectric constant and dielectric loss tangent of the hollow particles tend to be. In recent years, in the information processing of electronic devices, in order to transmit large-capacity information, efforts have been made to increase the transmission frequency, requiring the technology of low dielectric constant and low dielectric loss tangent that can cope with high-frequency transmission. By increasing the proportion of hydrocarbon monomer units in the polymer, hollow particles whose relative dielectric constant and dielectric loss tangent are fully reduced even at high frequencies of about 10 GHz can be made.
[0217] The hydrocarbon monomer units preferably contain at least a crosslinkable hydrocarbon monomer unit in order to improve the dielectric properties of the hollow particles and achieve excellent pressure resistance. In order to particularly improve the dielectric properties of the hollow particles, a crosslinkable hydrocarbon monomer unit and a non-crosslinkable hydrocarbon monomer unit are preferably contained in combination.
[0218] In the hollow particles of the present invention, the effect of reducing the dielectric loss tangent and improving the performance stability under a high-humidity environment brought about by the pH of the aqueous dispersion of the above-mentioned hollow particles being 6.5 to 7.5 and the electrical conductivity being 50 μS / cm or less can be particularly effectively exerted when the content of the hydrocarbon monomer units in the above-mentioned polymer constituting the shell is greater than 50% by mass, and can be more effectively exerted when the combination contains cross-linked hydrocarbon monomer units and non-cross-linked hydrocarbon monomer units.
[0219] The dielectric loss tangent of the hollow particles of the present invention at a frequency of 10 GHz is preferably 1.00×10 -3 Below, more preferably 9.00×10 -4 Below, more preferably 6.00×10 -4 Below, more preferably 4.00×10 -4 The lower limit of the dielectric loss tangent is not particularly limited, and may be, for example, 1.00×10 -4 above.
[0220] The relative dielectric constant of the hollow particles of the present invention at a frequency of 10 GHz is preferably 1.40 or less, more preferably 1.37 or less, and further preferably 1.35 or less. The lower limit is not particularly limited, and may be, for example, 1.00 or more.
[0221] In the present invention, the relative dielectric constant and dielectric loss tangent of the hollow particles can be measured using a perturbation type measuring device.
[0222] The porosity of the hollow particles of the present invention is 50% or more, preferably 60% or more, more preferably 65% or more, and more preferably 70% or more. By having a porosity of more than the above lower limit, the dielectric properties of the hollow particles are excellent, and then lightness, heat resistance and heat insulation are also excellent. The upper limit of the porosity of the hollow particles is not particularly limited, and from the aspect of suppressing the reduction of the strength of the hollow particles and not being easily broken, it is preferably 90% or less, more preferably 85% or less, and more preferably 80% or less.
[0223] The porosity of the hollow particles was calculated based on the apparent density D1 and true density D0 of the hollow particles.
[0224] The apparent density D1 of the hollow particles is measured as follows. First, a volume of 100 cm 3 Fill the volumetric flask to about 30 cm 3 The mass of the hollow particles filled was accurately weighed. Next, isopropyl alcohol was accurately filled to the mark in the volumetric flask filled with the hollow particles, while being careful not to allow air bubbles to enter. The mass of isopropyl alcohol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm2) of the hollow particles was calculated based on the following formula (I):3 ).
[0225] .
[0226] The apparent density D1 corresponds to the specific gravity of the entire hollow particle when the hollow portion is regarded as a part of the hollow particle.
[0227] The true density D0 of the hollow particles is determined as follows. The hollow particles are crushed in advance and then placed in a 100 cm 3 A volumetric flask is filled with about 10 g of hollow particle fragments, and the mass of the filled fragments is accurately weighed. Then, isopropyl alcohol is added to the volumetric flask in the same manner as the above-mentioned apparent density measurement, and the mass of isopropyl alcohol is accurately weighed. The true density D0 (g / cm 3 ).
[0228] .
[0229] The true density D0 corresponds to the specific gravity of only the shell portion of the hollow particle. As can be seen from the above measurement method, the hollow portion is not considered as a part of the hollow particle when calculating the true density D0.
[0230] The porosity (%) of the hollow particles is calculated from the apparent density D1 and true density D0 of the hollow particles by the following formula (III).
[0231] .
[0232] The lower limit of the volume average particle size of the hollow particles of the present invention is preferably 1.0 μm or more, more preferably 1.5 μm or more, and further preferably 2.0 μm or more. On the other hand, the upper limit of the volume average particle size of the hollow particles is preferably 10.0 μm or less, more preferably 8.0 μm or less, more preferably 6.0 μm or less, and further preferably 4.0 μm or less. When the volume average particle size of the hollow particles is above the above lower limit, the unevenness of the shell thickness can be suppressed, a uniform shell is easily formed, and the hollow particles become difficult to break, and therefore have high mechanical strength. When the volume average particle size of the hollow particles is below the above upper limit, since the particle size is small enough, it is preferably used as a substrate material such as a circuit substrate, and can also be added to a small substrate with a thin thickness.
[0233] The shape of the hollow particles of the present invention is not particularly limited as long as a hollow portion is formed inside, and examples thereof include spherical, ellipsoidal, and irregular shapes, etc. Among these, a spherical shape is preferred from the viewpoint of ease of production and pressure resistance.
[0234] The hollow particles of the present invention may have one or two or more hollow parts, but preferably have only one hollow part from the viewpoint of maintaining a good balance between high porosity and mechanical strength and improving dielectric properties.
[0235] In the case where the hollow particles of the present invention have only one hollow part, the hollow particles of the present invention may contain a small amount of hollow particles having two or more hollow parts or particles having no hollow part as impurities. In the hollow particles of the present invention, the number ratio of particles having only one hollow part is preferably 90% or more, more preferably 95% or more.
[0236] Furthermore, the shell of the hollow particles of the present invention and, when the hollow particles have two or more hollow parts, the partition walls separating adjacent hollow parts may be porous, but are preferably dense from the viewpoint of improving dielectric properties.
[0237] The average circularity of the hollow particles of the present invention may be 0.950 to 0.995.
[0238] An example of the shape of the hollow particles of the present invention is a bag formed by a thin membrane and filled with gas, and its cross-sectional view is as follows: Figure 1 In this example, a thin film is provided on the outside, and the inside is filled with gas.
[0239] In addition, the particle shape can be confirmed by, for example, SEM or TEM.
[0240] In addition, from the viewpoint of dielectric properties and pressure resistance, the hollow particles of the present invention preferably have a small proportion of particles with a roundness of less than 0.85. Particles with a roundness of less than 0.85 are usually particles that produce deformations such as depressions and ruptures, and are sometimes referred to as "special-shaped particles" in the present invention. Such special-shaped hollow particles have low porosity compared to spherical hollow particles, so the dielectric properties are poor. Therefore, by reducing the proportion of special-shaped particles included in the hollow particles, the dielectric properties of the hollow particles can be improved.
[0241] In addition, since irregular particles are easily subjected to external pressure locally, their pressure resistance is worse than that of spherical particles. Furthermore, compared with spherical particles, irregular particles have the problem of being easily agglomerated and having poor dispersibility when dispersed in the matrix resin. When irregular particles are dispersed in the matrix resin, agglomerates are easily generated, and the agglomerates are easily subjected to external pressure, resulting in worse pressure resistance. Therefore, by reducing the proportion of irregular particles contained in hollow particles, the dispersibility and pressure resistance of hollow particles can be improved.
[0242] The hollow particles of the present invention may contain a small amount of particles with low roundness due to particle breakage, deformation, etc. as impurities. Among 100% by mass of the hollow particles of the present invention, the proportion of particles with a roundness of 0.85 or less is preferably 10% by mass or less, more preferably 7% by mass or less, further preferably 5% by mass or less, further preferably 4% by mass or less, and particularly preferably 3% by mass or less.
[0243] The roundness is defined as the value obtained by dividing the diameter of a circle having the same area as the projection image of the particle (equivalent diameter of the circle area) by the diameter of a circle having the same circumference as the projection image of the particle (equivalent diameter of the circumference). When the particle is a perfect sphere, the roundness is 1, and the more complex the surface shape of the particle, the smaller the roundness value.
[0244] In the present invention, the circularity is measured using a flow-type particle image measuring device at an image resolution of 0.185 μm / pixel.
[0245] As a flow type particle image measuring device, for example, the product name "IF-3200" manufactured by Jasco International Co., Ltd. can be preferably used. The measurement sample is prepared, for example, by adding 0.10 to 0.12 g of hollow particles to an aqueous solution of sodium linear alkylbenzene sulfonate (concentration 0.3%) and dispersing the mixture for 5 minutes using an ultrasonic cleaner.
[0246] The average circularity is the average value of the circularities of 1,000 to 3,000 particles selected at random.
[0247] The particle size distribution (volume average particle size (Dv) / number average particle size (Dn)) of the hollow particles can be, for example, 1.1 or more and 2.5 or less. By having the particle size distribution be 2.5 or less, particles with small uneven performance between particles can be obtained. In addition, by having the particle size distribution be 2.5 or less, it is possible to produce a product with uniform thickness when, for example, manufacturing a sheet-like resin molded body to which the hollow particles of the present invention are added.
[0248] The volume average particle size (Dv) and number average particle size (Dn) of the hollow particles can be obtained, for example, by measuring the particle size of the hollow particles by a particle size distribution measuring device, calculating the number average and volume average, respectively, and using the obtained values as the number average particle size (Dn) and volume average particle size (Dv) of the particles. The particle size distribution is the value obtained by dividing the volume average particle size by the number average particle size.
[0249] In the present invention, the thermal decomposition starting temperature of the hollow particles is preferably 150 to 400° C., and more preferably 200 to 350° C. The hollow particles having a thermal decomposition starting temperature within the above range have excellent heat resistance.
[0250] In the present invention, the thermal decomposition starting temperature of the hollow particles is the temperature at which the weight is reduced by 5%, and can be measured by a TG-DTA apparatus in an air atmosphere at an air flow rate of 230 mL / min and a temperature increase rate of 10° C. / min.
[0251] 3. Application of hollow particles
[0252] As the purpose of the hollow particles of the present invention, for example, components of low dielectric materials, heat insulation materials, sound insulation materials and light reflective materials used in various fields such as automobiles, electrical, electronic, construction, aviation, aerospace, etc., food containers, sports shoes, sandals and other footwear, home appliance parts, bicycle parts, stationery, tools, 3D printer filaments, composite foam and other buoyancy materials, etc. can be cited. The hollow particles of the present invention are particularly preferably used as materials with high reliability in electrical or electronic fields because of their small dielectric loss tangent, excellent dielectric properties and excellent performance stability under high humidity environments. For example, the hollow particles of the present invention are preferably used as circuit substrate materials. Specifically, by making the insulating resin layer of the circuit substrate contain the hollow particles of the present invention, it is possible to reduce the dielectric loss tangent of the insulating resin layer and suppress the faults such as ion migration under high humidity environments.
[0253] In addition, the hollow particles of the present invention are also preferably used as interlayer insulating materials, dry film resists, solder resists, bonding wires, magnetic wires, semiconductor sealing materials, epoxy sealing materials, molded bottom filling glue, bottom filling glue, chip soldering paste, buffer coating materials, copper-clad laminates, flexible substrates and other semiconductor materials, or high-frequency component modules, antenna modules, vehicle-mounted radars and other semiconductor materials used additives. Among these, it is particularly preferred as an additive for semiconductor materials such as interlayer insulating materials, solder resists, magnetic wires, semiconductor sealing materials, epoxy sealing materials, bottom filling glue, buffer coating materials, copper-clad laminates, flexible substrates, or high-frequency component modules, antenna modules, vehicle-mounted radars and other semiconductor materials. In addition, the hollow particles of the present invention are not limited to semiconductor materials, and can be used for various electronic materials.
[0254] In addition, the hollow particles of the present invention are also useful as additives for insulating resin sheets used in the manufacture of electronic components such as printed wiring boards. The insulating resin sheet containing the hollow particles of the present invention can be manufactured by, for example, the following method: preparing a resin composition mixed with a thermoplastic resin, a thermosetting resin, a thermoplastic elastomer, or a mixture thereof and the hollow particles of the present invention, and applying the resin composition to one or both sides of a sheet substrate for drying, extrusion molding, or transfer molding into a sheet. In the case where the resin or elastomer contained in the insulating resin sheet has adhesiveness, the insulating resin sheet can be used as an adhesive sheet, specifically, can be used as, for example, a bonding sheet. In the case of manufacturing a multilayer printed wiring substrate, the bonding sheet is an insulating adhesive layer forming material for bonding a conductor layer to an organic insulating layer.
[0255] The hollow particles of the present invention have excellent strength because they contain sufficient crosslinkable monomer units in the shell, so they are not easily broken when kneaded with other materials or molded after kneading. When added to a molded body, they have excellent effects as a low dielectric material, a lightweight material, a heat insulating material, a sound insulating material, a shockproof material, etc. Therefore, they can be preferably used as an additive for a molded body, for example, as an additive for a resin molded body.
[0256] Examples of the resin to which the hollow particles of the present invention can be added, i.e., the matrix resin, include polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyurethane, epoxy resin, acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-styrene (AS) resin, poly(meth)acrylate, polycarbonate, polyamide, polyimide, polyphenylene ether, polyphenylene sulfide, polyester, polytetrafluoroethylene, maleimide resin, bismaleimide triazine resin, liquid crystalline polyester resin, phenolic resin, vinyl ester resin, unsaturated polyester resin, cyanate resin, polyetherketoneketone resin, polyetherimide resin and other thermoplastic resins or thermosetting resins.
[0257] In the case of resin molded articles requiring low dielectric loss tangent, epoxy resin, thermosetting modified polyphenylene ether resin, thermosetting polyimide resin, silicone resin, benzophenone resin, etc. are particularly preferably used as the matrix resin. Insulating resins such as azine resin, melamine resin, urea resin, allyl resin, phenolic resin, unsaturated polyester resin, polyurethane resin, and aniline resin.
[0258] When an epoxy resin is used as the matrix resin, it is preferable to appropriately mix a curing agent such as an amine, an acid anhydride, or an imidazole, a curing accelerator, or a catalyst.
[0259] In addition, the hollow particles of the present invention can also be contained as fillers in a fiber-reinforced molded body formed using a resin and reinforcing fibers. The reinforcing fibers are not particularly limited, and organic or inorganic fibers such as carbon fibers, glass fibers, aramid fibers, and polyethylene fibers can be cited.
[0260] In addition, the hollow particles of the present invention have high porosity, are not easily broken, and have excellent heat resistance, so they meet the heat insulation and cushioning (shock absorption) required by the base coating material, and also meet the heat resistance suitable for thermal paper purposes. In addition, the hollow particles of the present invention are also useful as plastic pigments excellent in gloss, shielding ability, etc.
[0261] Furthermore, the hollow particles of the present invention can contain useful components such as fragrances, drugs, pesticides, and ink components by methods such as impregnation treatment, reduced pressure or pressurized impregnation treatment, and can therefore be used for various purposes depending on the components contained therein.
[0262] Furthermore, the hollow particles of the present invention are also preferably used as rust preventives. Since the hollow particles of the present invention are also useful as additives that reduce electrical conductivity, for example, a coating containing the hollow particles of the present invention can be used as an anti-rust coating (coating primer, lubricating coating, etc.) for improving the corrosion resistance and rust resistance of steel materials, etc. In addition, the hollow particles added to the anti-rust coating can also contain an anti-rust additive.
[0263] Hereinafter, the resin composition and the resin molded article containing the hollow particles of the present invention will be described in further detail.
[0264] 4. Resin composition
[0265] The resin composition of the present invention is characterized by comprising the hollow particles of the present invention and a matrix resin.
[0266] The resin composition of the present invention is generally used as a molding material for a resin molded body described below, and may be in the form of, for example, a liquid or pellet form, or may be a prepreg.
[0267] As liquid resin compositions, for example, resin compositions comprising liquid matrix resins before the curing reaction, resin compositions obtained by dissolving or dispersing various components in a solvent, etc. can be cited. Here, the liquid matrix resins before the curing reaction and the matrix resins dissolved or dispersed in a solvent can be thermosetting resins or thermoplastic resins. Alternatively, the resin composition can be made liquid by melting the matrix resin. Prepregs can be obtained by, for example, impregnating a liquid resin composition into a substrate and drying it. As granular resin compositions, for example, resin compositions obtained by melt-kneading a thermoplastic matrix resin and hollow particles, and resin compositions obtained by making them into granules when cooled and solidified can be cited.
[0268] As mentioned above, hollow particles of the present invention reduce dielectric loss tangent and improve performance stability under high humidity. Compared with the situation that does not contain hollow particles, the resin composition and resin molding containing existing hollow particles have the tendency that performance stability under high humidity is reduced. On the contrary, the resin composition and resin molding containing hollow particles of the present invention suppress the reduction of performance stability under high humidity by containing hollow particles of the present invention while reducing dielectric loss tangent.
[0269] Examples of the matrix resin contained in the resin composition of the present invention include the same resins as those that can be added to the hollow particles of the present invention described above.
[0270] The matrix resin contained in the resin composition of the present invention may be, for example, a curable resin such as a thermosetting resin, a photocurable resin, or a room temperature curable resin, or a thermoplastic resin.
[0271] In addition, the matrix resin contained in the resin composition of the present invention can be an unreacted monomer, prepolymer or macromonomer, or a polymer, or a precursor of a curing resin such as polyamic acid, without particular limitation. The matrix resin contained in the resin composition of the present invention can be a resin that functions as a binder by, for example, heating, light irradiation, or curing using a curing agent, a polymerization initiator or a catalyst.
[0272] As the thermosetting resin, known thermosetting resins can be used without particular limitation, and examples thereof include phenolic resins, melamine resins, urea resins, unsaturated polyester resins, epoxy resins, polyurethane resins, silicone resins, alkyd resins, thermosetting modified polyphenylene ether resins, thermosetting polyimide resins, benzophenone resins, Oxazine resin, allyl resin, aniline resin, maleimide resin, bismaleimide triazine resin, liquid crystalline polyester resin, vinyl ester resin, unsaturated polyester resin, cyanate resin, polyetherketoneketone resin, polyetherimide resin, and precursors of these resins before curing. These thermosetting resins can be used alone or in combination of two or more.
[0273] Examples of the room temperature curable resin include adhesives that can be cured at room temperature by adding a catalyst, such as epoxy adhesives, silicone adhesives, and acrylic adhesives.
[0274] Examples of thermoplastic resins include polyolefin resins, polyamide resins, polycarbonate resins, polyphenylene sulfide resins, polyetheretherketone resins, polystyrene resins, polyphenylene ether resins, and liquid crystal polymers (LCP). Examples of thermoplastic resins include polyolefins such as polypropylene and polyethylene; polyamides such as PA6, PA66, and PA12; polyimides, polyamideimides, polyetherimides, polyetherketoneketones, polyvinyl chloride, polystyrene, poly(meth)acrylates, polycarbonates, polyvinylidene fluoride, acrylonitrile-butadiene-styrene copolymers (ABS) resins, acrylonitrile-styrene copolymers (AS), polyphenylene ethers, polyphenylene sulfides, polyesters, polytetrafluoroethylene, and thermoplastic elastomers. In addition, thermoplastic elastomers generally refer to substances that have the property of showing rubber elasticity at room temperature (25° C.) and being plasticized and molded at high temperatures. Examples of the thermoplastic elastomer include polyurethane elastomers, styrene elastomers, olefin elastomers, amide elastomers, and ester elastomers.
[0275] The matrix resin contained in the resin composition of the present invention can be appropriately selected according to the application and is not particularly limited. The resin composition of the present invention may contain one matrix resin alone or two or more matrix resins in combination.
[0276] In the resin composition of the present invention, the content of the matrix resin is not particularly limited, and is preferably 20 to 99 parts by mass, more preferably 30 to 95 parts by mass, and further preferably 40 to 95 parts by mass relative to the total solid content of 100 parts by mass contained in the resin composition. When the content of the matrix resin is above the above lower limit, the moldability when the resin molded body is made is improved, and the mechanical strength of the obtained resin molded body is improved. On the other hand, by having the content of the matrix resin below the above upper limit, the hollow particles of the present invention can be fully contained, so the effects such as the improvement of dielectric properties brought by the hollow particles of the present invention can be fully exerted.
[0277] The resin composition of the present invention may further contain additives such as a curing agent, a curing accelerator, a curing catalyst, or an initiator for curing reaction, which can be appropriately selected from known substances according to the type of the base resin and are not particularly limited.
[0278] The content of the curing agent is not particularly limited, and may be, for example, 1 to 120 parts by mass relative to 100 parts by mass of the base resin.
[0279] The content of the curing accelerator is not particularly limited, and may be, for example, 0.01 to 10 parts by mass based on 100 parts by mass of the base resin.
[0280] In the resin composition of the present invention, the content of hollow particles is not particularly limited, and relative to the total solid content of 100 parts by mass contained in the resin composition, it is preferably 1 to 70 parts by mass, more preferably 3 to 50 parts by mass, and further preferably 5 to 40 parts by mass. By the content of hollow particles being above the above lower limit, the effects such as the improvement of dielectric properties brought by the hollow particles of the present invention can be fully exerted. On the other hand, by making the content of hollow particles below the above upper limit, it is possible to fully contain the matrix resin, so that moldability and mechanical strength can be improved.
[0281] The resin composition of the present invention can further include reinforcing fibers. As reinforcing fibers, organic or inorganic fibers such as carbon fibers, glass fibers, aramid fibers, polyethylene fibers, cellulose nanofibers, liquid crystal polymer (LCP) fibers can be cited. As reinforcing fibers, at least one of carbon fibers and glass fibers is particularly preferably selected.
[0282] Furthermore, the reinforcing fiber contained in the resin composition of the present invention may be used as a base material of a prepreg, or may be contained as a filler.
[0283] In the case where the resin combination of the present invention includes fortifying fiber, the content of fortifying fiber is relative to 100 mass parts of the total of hollow particles and matrix resin, as the lower limit, preferably more than 5 mass parts, more preferably more than 10 mass parts, as the upper limit, preferably below 200 mass parts, more preferably below 150 mass parts. When the content of fortifying fiber is above the above lower limit, the strength improvement effect brought by fortifying fiber is excellent. On the other hand, when the content of fortifying fiber is below the above upper limit, matrix resin and hollow particles can be fully contained, therefore formability and lightness and dielectric properties etc. can be improved.
[0284] The resin composition of the present invention may further contain a solvent. As the solvent, a known solvent can be used, and the solvent may be appropriately selected according to the type of the matrix resin.
[0285] When the resin composition of the present invention contains a solvent, the solid content concentration of the resin composition of the present invention is preferably 10 to 90% by mass.
[0286] The resin composition of the present invention may further contain fillers, coupling agents, low stress agents, defoamers, leveling agents, ultraviolet absorbers, foaming agents, antioxidants, colorants, heat stabilizers, flame retardants and other additives as needed without impairing the effects of the present invention.
[0287] The resin composition of the present invention can be obtained by, for example, mixing the hollow particles of the present invention, the matrix resin, and other components further added as needed. The mixing method is not particularly limited, and a method using a known mixing device such as a planetary mixer, a ball mill, a bead mill, a planetary agitator, a roller mill, etc. can be adopted.
[0288] When the matrix resin is a thermoplastic resin, the resin composition of the present invention can be obtained by adding the hollow particles of the present invention and other components added as needed to a molten matrix resin (thermoplastic resin) and melt-kneading the mixture.
[0289] In addition, the resin varnish obtained by mixing the hollow particles of the present invention, the matrix resin and other components further added as needed is impregnated in the base material and dried, thus prepreg can be obtained. As the above-mentioned base material, inorganic fibers such as carbon fiber, glass fiber, metal fiber, ceramic fiber and organic synthetic fibers such as polyamide fiber, polyester fiber, polyolefin fiber, Novoloid fiber, etc. can be cited, especially glass fiber (glass cloth). In addition, the form of the above-mentioned base material is not limited, and fabrics, nonwoven fabrics, etc. can be used.
[0290] 5. Resin molding
[0291] The resin molded article of the present invention is a resin molded article obtained from the above-mentioned resin composition of the present invention.
[0292] The method for obtaining a resin molded body from the resin composition of the present invention can be appropriately selected from known methods according to the type of matrix resin contained in the resin composition, the form of the resin composition, etc., and is not particularly limited. In the case where the resin composition of the present invention contains a curable resin as the matrix resin, the resin molded body of the present invention contains a cured product of the resin composition.
[0293] When the resin composition of the present invention is a varnish, for example, the resin composition can be applied to a support, dried and cured as required to obtain a resin molded body. In addition, the support can be, for example, made of resin or metal, and a release agent can also be applied to the surface of the support.
[0294] As a method for applying the resin composition, a known method can be used, and examples thereof include dip coating, roll coating, curtain coating, die coating, slit coating, and gravure coating.
[0295] When the resin composition contains a solvent, it is preferred to dry the resin composition after the above-mentioned coating. The drying temperature is preferably a temperature at which the matrix resin does not solidify, usually 20° C. or more and 200° C. or less, preferably 30° C. or more and 150° C. or less. In addition, the drying time is usually 30 seconds or more and 1 hour or less, preferably 1 minute or more and 30 minutes or less.
[0296] The curing reaction of the resin composition is carried out by a method corresponding to the type of the matrix resin, without particular limitation. In the case of a matrix resin that is cured by heating, the heating temperature for the curing reaction can be appropriately adjusted according to the type of resin, without particular limitation, and is usually above 30°C and below 400°C, preferably above 70°C and below 300°C, and more preferably above 100°C and below 200°C. In addition, the curing time is from 5 minutes to 5 hours, preferably from 30 minutes to 3 hours. The heating method is not particularly limited, for example, it can be carried out using an electric oven.
[0297] When the resin composition of the present invention is a prepreg, a resin molded body can be obtained by curing the prepreg.
[0298] Preferred conditions for curing the prepreg are the same as the preferred conditions for curing the above-mentioned resin composition.
[0299] In the case of a resin composition of the present invention that is a granular resin composition containing a thermoplastic matrix resin, the resin composition can be melt-kneaded, for example, and then molded into a desired shape by known molding methods such as extrusion molding, injection molding, compression molding, and compression molding to obtain a resin molded body of the present invention. The temperature during melt kneading is not particularly limited as long as it is a temperature at which the thermoplastic resin used can be melted. In addition, kneading can be carried out by a known method, is not particularly limited, and can be carried out using a kneading device such as a single-axis kneader or a double-axis kneader.
[0300] The shape of the resin molded article of the present invention is not particularly limited, and may be various shapes that can be molded, for example, any shape such as a sheet, a film, a plate, a tube, and other various three-dimensional shapes.
[0301] As the applications of the resin composition and the resin molded article of the present invention, for example, applications in which the resin composition or the resin molded article can be used among the applications of the hollow particles of the present invention described above can be mentioned.
[0302] Hereinafter, one embodiment of the resin composition of the present invention used as a semiconductor sealing material in the above-mentioned application (hereinafter referred to as "sealing resin composition") will be described in detail.
[0303] 6. Sealing resin composition
[0304] The sealing resin composition of the present invention is a resin composition of the present invention used as a sealing material for a semiconductor device or the like.
[0305] The sealing resin composition of the present invention is characterized by comprising an epoxy resin as a matrix resin. That is, the sealing resin composition of the present invention is characterized by comprising the hollow particles of the present invention and an epoxy resin.
[0306] By using an epoxy resin as a base resin, it is possible to obtain a resin composition that satisfies the moisture resistance and heat resistance required of a sealing material.
[0307] Since the sealing resin composition of the present invention further contains the hollow particles of the present invention, the dielectric properties are improved and the performance stability is excellent in a high-humidity environment.
[0308] [Epoxy resin]
[0309] The epoxy resin contained in the sealing resin composition of the present invention may be a compound having one or more epoxy groups in the molecule. In addition, from the viewpoint of the workability during production and curing of the sealing resin composition of the present invention, the epoxy resin is preferably liquid at room temperature (25° C.).
[0310] The sealing resin composition of the present invention preferably contains at least an alicyclic epoxy resin as the epoxy resin, thereby improving the performance of the resin composition, such as moisture resistance, dielectric properties, and heat resistance.
[0311] Alicyclic epoxy resins are compounds having one or more alicyclic rings (aliphatic hydrocarbon rings) and one or more epoxy groups in the molecule. As alicyclic epoxy compounds, from the aspect of the above-mentioned excellent performance, (i) compounds having at least one alicyclic epoxy group in the molecule are particularly preferred. In addition, as such compounds, compounds having two or more alicyclic epoxy groups in the molecule are more preferred.
[0312] In the above (i) compound having at least one alicyclic epoxy group in the molecule, the alicyclic epoxy group refers to an epoxy group consisting of two adjacent carbon atoms and oxygen atoms constituting an alicyclic ring. The alicyclic epoxy group is not particularly limited, but from the viewpoint of curability, a cyclohexene oxide group is preferably an epoxy group consisting of two adjacent carbon atoms and oxygen atoms constituting a cyclohexane ring.
[0313] As the compound (i) having at least one alicyclic epoxy group in the molecule, from the viewpoint of heat resistance of the cured product, a compound having two or more cyclohexyl oxide groups in the molecule is preferred, and a compound represented by the following formula (A) is more preferred. In addition, one or more carbon atoms constituting the alicyclic epoxy group in the following formula (A) may be bonded to a substituent such as an alkyl group having 1 to 6 carbon atoms.
[0314] [Chemical formula 1]
[0315] .
[0316] In the above formula (A), X represents a single bond or a linking group, preferably a linking group. Here, the linking group refers to a divalent group having one or more atoms.
[0317] As the above-mentioned linking group, for example, a divalent hydrocarbon group, a carbonyl group, an ether bond, an ester bond, a carbonate group, an amide bond, and a group formed by connecting two or more of them can be cited. As the above-mentioned linking group, a linking group containing an oxygen atom is particularly preferred, and a linking group containing an ester bond is more preferred. Particularly preferred is a group formed by connecting at least one ester bond and a linear alkylene group having 1 to 18 carbon atoms, and more preferably a group formed by connecting an ester bond and a linear alkylene group having 1 to 6 carbon atoms.
[0318] The compound represented by the above formula (A) is not particularly limited, and examples thereof include (3,3′,4,4′-diepoxy)bicyclohexane, 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexylcarboxylate, ε-caprolactone-modified 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexylcarboxylate, 2,2-bis(3,4-epoxycyclohexane-1-yl)propane, bis(3,4-epoxycyclohexylmethyl)ether, 1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, and 1,2-epoxy-1,2-bis(3,4-epoxycyclohexane-1-yl)ethane. In particular, 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexylcarboxylate is particularly preferably used.
[0319] As the compound represented by the above formula (A), commercially available products such as "CELLOXIDE 2021P" (compound name: 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexylcarboxylate), "CELLOXIDE 2081" (compound name: caprolactone-modified 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexylcarboxylate), "CELLOXIDE 8000" (compound name: (3,3',4,4'-diepoxy)bicyclohexane), and "EPOLEAD GT401" manufactured by Daicel Corporation can also be used.
[0320] Among the compounds having at least one alicyclic epoxy group in the molecule (i), compounds having two or more alicyclic epoxy groups in the molecule include, in addition to the compounds represented by the above formula (A), compounds having cyclohexyl oxide and cyclopentyl oxide in the molecule. Such compounds include, for example, EPOCHALIC (registered trademark) THI-DE, DE-102 and DE-103 manufactured by Ennos Corporation.
[0321] Among the compounds having at least one alicyclic epoxy group in the molecule (i) above, examples of the compounds having one alicyclic epoxy group in the molecule include "CYCLOMER M100" and "CELLOXIDE 2000" manufactured by Daicel Corporation.
[0322] As the alicyclic epoxy compound, (ii) a compound having an epoxy group directly bonded to an alicyclic ring by a single bond can also be used. Such a compound is not particularly limited, and examples thereof include 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (e.g., product name "EHPE3150" manufactured by Daicel Corporation).
[0323] As the alicyclic epoxy compound, (iii) a compound having an alicyclic ring and a glycidyl group can also be used. The compound is not particularly limited, and examples thereof include 2,2-bis[4-(2,3-epoxypropoxy)cyclohexyl]propane, 2,2-bis[3,5-dimethyl-4-(2,3-epoxypropoxy)cyclohexyl]propane, hydrogenated bisphenol A type epoxy resin, bis[2-(2,3-epoxypropoxy)cyclohexyl]methane, [2-(2,3-epoxypropoxy)cyclohexyl][4-(2,3-epoxypropoxy)cyclohexyl]methane, bis[4-(2,3-epoxypropoxy)cyclohexyl]methane, bis[3,5-dimethyl-4-(2,3-epoxypropoxy)cyclohexyl]methane, hydrogenated bisphenol F type epoxy resin, hydrogenated biphenol type epoxy resin, hydrogenated novolac type epoxy resin, and hydrogenated naphthalene type epoxy resin.
[0324] In addition, the alicyclic epoxy resin can be used alone or in combination of two or more.
[0325] The sealing resin composition of the present invention may also contain an epoxy resin without an alicyclic structure as the epoxy resin. By appropriately selecting the epoxy resin without an alicyclic structure, the sealing resin composition of the present invention can be given desired properties. For example, by selecting a resin with high flexibility as the epoxy resin without an alicyclic structure, the sealing resin composition of the present invention can be given stress relaxation properties.
[0326] The epoxy resin not having an alicyclic structure is not particularly limited, and examples thereof include biphenylol-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol S-type epoxy resins, bisphenol AF-type epoxy resins, trisphenol-type epoxy resins, naphthol novolac-type epoxy resins, phenol novolac-type epoxy resins, tert-butyl-catechol-type epoxy resins, naphthalene-type epoxy resins, naphthol-type epoxy resins, anthracene-type epoxy resins, glycidylamine-type epoxy resins, glycidylester-type epoxy resins, cresol novolac-type epoxy resins, biphenyl-type epoxy resins, biphenylaralkyl-type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, heterocyclic epoxy resins, spiro ring-containing epoxy resins, naphthylene ether-type epoxy resins, trimethylol-type epoxy resins, tetraphenylethane-type epoxy resins, and the like. Among these, bisphenol A type epoxy resin is preferred from the viewpoint of improving the followability to unevenness when sealing semiconductor elements, that is, the unevenness embedding property. On the other hand, biphenyl aralkyl type epoxy resin is preferred from the viewpoint of heat resistance.
[0327] Furthermore, from the viewpoint of reactivity, the epoxy resin not having an alicyclic structure preferably has two or more epoxy groups in the molecule.
[0328] The epoxy resins not having an alicyclic structure may be used alone or in combination of two or more.
[0329] In the sealing resin composition of the present invention, from the perspective of improving performance such as moisture resistance, dielectric properties and heat resistance, the content of the alicyclic epoxy resin in 100 parts by mass of the epoxy resin is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and further preferably 50 parts by mass or more.
[0330] In the sealing resin composition of the present invention, from the perspective of improving performance such as moisture resistance, dielectric properties and heat resistance, the content of 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexylcarboxylate in 100 parts by mass of the epoxy resin is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and further preferably 50 parts by mass or more.
[0331] In the sealing resin composition of the present invention, the content of the epoxy resin is not particularly limited. From the viewpoint of uneven embedding properties, the content is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and further preferably 40 parts by mass or more, relative to 100 parts by mass of the total solid content contained in the sealing resin composition. On the other hand, from the perspective of suppressing deterioration of dielectric properties, the content is preferably 95 parts by mass or less, more preferably 90 parts by mass or less, and further preferably 80 parts by mass or less.
[0332] [Hollow particles]
[0333] The hollow particles contained in the sealing resin composition of the present invention are the above-mentioned hollow particles of the present invention.
[0334] In the sealing resin composition of the present invention, the content of hollow particles is not particularly limited, and from the perspective of suppressing the reduction of performance stability while improving the dielectric properties of the resin composition, it is preferably 1 to 70 parts by mass relative to the total solid content of 100 parts by mass contained in the resin composition. From the perspective of improving the dielectric properties of the resin composition, the lower limit of the content of hollow particles is more preferably 3 parts by mass or more, and more preferably 5 parts by mass or more. From the perspective of suppressing the reduction of the performance stability of the resin composition and suppressing the reduction of the concave-convex embedding property, the upper limit of the content of hollow particles is more preferably 50 parts by mass or less, and more preferably 40 parts by mass or less.
[0335] [Curing accelerator]
[0336] The sealing resin composition of the present invention usually contains a curing accelerator. As the curing accelerator, a substance commonly used as a curing accelerator for epoxy resin can be appropriately selected, and there is no particular limitation, and examples thereof include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators.
[0337] In addition, the curing accelerator can be used alone or in combination of two or more.
[0338] In the present invention, the curing accelerator is not particularly limited, and it is preferred to use an imidazole curing accelerator from the perspective of easily obtaining a resin composition with excellent heat resistance. Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-cyanoethyl-2-undecylimidazole. Trimellitate, 1-cyanoethyl-2-phenylimidazole Trimellitate, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2,4-diamino-6-[2′-undecylimidazolyl-(1′)]-ethyl-s-triazine, 2,4-diamino-6-[2′-ethyl-4′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazole Chloride, imidazole compounds such as 2-methylimidazoline and 2-phenylimidazoline, and adducts of imidazole compounds and epoxy resins. In particular, at least one selected from 2-ethyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, and 2-heptadecylimidazole is preferred.
[0339] In the sealing resin composition of the present invention, the content of the curing accelerator can be appropriately adjusted according to the type of the curing accelerator, and is not particularly limited. It is preferably 0.1 to 7 parts by mass, and more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the epoxy resin. When the content of the curing accelerator is above the above lower limit, the curing acceleration effect is excellent.
[0340] [Curing agent]
[0341] The sealing resin composition of the present invention preferably contains a curing agent. As the curing agent, a substance generally used as a curing agent for epoxy resin can be appropriately selected, and there is no particular limitation, and examples thereof include amine curing agents, acid anhydride curing agents, imidazole curing agents, thiol curing agents, phenol curing agents, naphthol curing agents, benzophenone curing agents, Oxazine-based curing agents, cyanate-based curing agents, and carbodiimide-based curing agents, etc. The curing agent can be used alone or in combination of two or more.
[0342] From the aspect that the storage stability of the sealing resin composition of the present invention becomes good, as a curing agent, an anhydride curing agent is preferably used. As an anhydride curing agent, it is not particularly limited, and for example hexahydrophthalic anhydride, methyl hexahydrophthalic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, methyl tetrahydrophthalic anhydride, methyl intramethylene tetrahydrophthalic anhydride, cyclohexane -1,2,4-tricarboxylic acid -1,2-anhydride, dodecenyl succinic anhydride, succinic anhydride, hydrogenated pyromellitic anhydride, hydrogenated biphenyl dianhydride, phthalic anhydride, tetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, etc. can be cited. From the aspect that the storage stability of the sealing resin composition is improved, it is particularly preferred to be selected from at least one of methyl hexahydrophthalic anhydride and methyl tetrahydrophthalic anhydride.
[0343] In the sealing resin composition of the present invention, the content of the curing agent can be appropriately adjusted according to the type of the curing agent, and is not particularly limited. The curing agent is preferably 0.5 to 1.5 equivalents, more preferably 0.8 to 1.2 equivalents, relative to 1 equivalent of epoxy group of the epoxy resin. In addition, in the acid anhydride curing agent, one acid anhydride group is calculated as 1 equivalent.
[0344] In the sealing resin composition of the present invention, the content of the curing agent is preferably 50 to 200 parts by mass, more preferably 70 to 120 parts by mass, based on 100 parts by mass of the epoxy resin.
[0345] [Other additives]
[0346] The sealing resin composition of the present invention may further contain additives commonly used in semiconductor sealing materials, such as release agents, plasticizers, fillers, antioxidants, light stabilizers, defoamers, leveling agents, coupling agents, surfactants, flame retardants, colorants, ion adsorbents, etc.
[0347] The release agent is not particularly limited, and examples thereof include long-chain carboxylic acids such as stearic acid, behenic acid, and montanic acid, or metal salts thereof; higher alcohols such as stearyl alcohol; amides such as stearyl diamide; esters such as carnauba wax and phosphate esters; paraffin wax; silicone oils such as dimethyl silicone oil and methylphenyl silicone oil, etc. These can be used alone or in combination of two or more.
[0348] The content of the release agent is not particularly limited, and can be, for example, 1 to 8 parts by mass relative to 100 parts by mass of the epoxy resin. When the sealing resin composition of the present invention contains a release agent, the slidability of the cured product can be improved.
[0349] The plasticizer is not particularly limited, and examples thereof include polyhydric alcohols. Examples of the polyhydric alcohol include glycerin, sorbitol, polyglycerol, pentaerythritol, and trimethylolpropane.
[0350] The content of the plasticizer is not particularly limited, and can be, for example, 5 to 30 parts by mass relative to 100 parts by mass of the epoxy resin.
[0351] The filler can be any of an inorganic or organic filler, preferably an inorganic filler. As the inorganic filler, there is no particular limitation, and examples thereof include barium sulfate, barium titanate, silicon dioxide (amorphous silicon dioxide, crystalline silicon dioxide, fused silica, spherical silicon dioxide, etc.), talc, clay, magnesium carbonate, calcium carbonate, aluminum oxide, aluminum hydroxide, silicon nitride, aluminum nitride, etc. In terms of good dispersibility, having a small thermal expansion coefficient, and being easy to obtain desired cured film properties, silicon dioxide is particularly preferably used.
[0352] The filler may be surface-modified. The surface modification method is not particularly limited, but surface modification using a silane coupling agent is preferred because it is simple, has a wide variety of functional groups, and can easily impart desired properties.
[0353] The content of the filler is not particularly limited, and can be, for example, 30% by volume or more and 85% by volume or less based on the total solid content contained in the sealing resin composition.
[0354] [Method for producing sealing resin composition]
[0355] The sealing resin composition of the present invention can be obtained by, for example, mixing the above-mentioned epoxy resin, hollow particles, curing accelerator, and curing agent and other additives as required by a known method. As a mixing method, for example, a method using a known mixing device or a mixing device such as a planetary mixer, a ball mill, a bead mill, a planetary mixer, a roller mill, a mixing extruder, a kneader, etc. can be cited. In addition, the sealing resin composition of the present invention can further contain a solvent as required.
[0356] Furthermore, the sealing resin composition of the present invention may be in a B-stage state.
[0357] [cured material]
[0358] The cured product of the sealing resin composition of the present invention can be obtained by, for example, heating the sealing resin composition of the present invention described above. The description of the heating temperature, curing time and heating method for curing the sealing resin composition of the present invention is the same as that of the resin composition of the present invention described above.
[0359] 7. Semiconductor devices
[0360] The semiconductor device of the present invention is characterized by comprising a cured product of the sealing resin composition of the present invention as a sealing material.
[0361] The semiconductor device of the present invention generally has a structure in which a semiconductor element is arranged on a substrate and the semiconductor element is sealed with a sealing material.
[0362] The method for sealing a semiconductor element disposed on a substrate using the sealing resin composition of the present invention is not particularly limited, and various molding methods such as transfer molding and cast molding can be employed.
[0363] Example
[0364] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts and % are based on mass unless otherwise specified.
[0365] [Example 1]
[0366] (1) Mixed solution preparation process
[0367] First, the following materials were mixed to prepare an oil phase.
[0368] 37.5 parts of divinylbenzene
[0369] 1.6 parts of ethylvinylbenzene
[0370] 0.89 parts of diethyl peroxy tert-butyl acetate
[0371] Hydrophobic solvent: 60.8 parts of heptane
[0372] Next, in a stirring tank, an aqueous solution obtained by dissolving 15.7 parts of magnesium chloride (water-soluble multivalent metal salt) in 225 parts of ion-exchanged water was slowly added with stirring to an aqueous solution obtained by dissolving 11.0 parts of sodium hydroxide (alkali metal hydroxide) in 55 parts of ion-exchanged water to prepare a magnesium hydroxide colloid (a metal hydroxide colloid that is sparingly soluble in water) dispersion (8 parts of magnesium hydroxide) to form an aqueous phase.
[0373] A mixed solution is prepared by mixing the obtained aqueous phase and oil phase.
[0374] (2) Suspension process
[0375] The mixed solution obtained in the mixed solution preparation step is stirred at 4000 rpm for 1 minute using an emulsifier disperser (manufactured by Plemix Co., Ltd., product name: Homomixer) to suspend it, thereby preparing a suspension in which droplets of the monomer composition containing a hydrophobic solvent are dispersed in water.
[0376] (3) Polymerization process
[0377] The suspension obtained in the above suspension step was heated to 80°C in a nitrogen atmosphere and stirred at 80°C for 24 hours to perform a polymerization reaction. The polymerization reaction obtained a slurry of precursor particles containing a hydrophobic solvent and dispersed in water, that is, a precursor composition.
[0378] (4) Cleaning process
[0379] The precursor composition obtained in the above-mentioned polymerization step is treated with dilute sulfuric acid (25°C, 10 minutes) to adjust the pH to below 5.5. After that, a nonionic surfactant is added to increase the affinity at the interface between water and the precursor particles, thereby eliminating the aggregation of the precursor particles to obtain a pH-adjusted slurry. Next, the precursor particles are separated from the pH-adjusted slurry by filtration while maintaining the room temperature (25°C), and the separated precursor particles are dehydrated. 200 parts of ion exchange water are newly added to the dehydrated precursor particles for re-slurrying, and the aggregation of the precursor particles is eliminated in the same manner as above, followed by filtration and dehydration. This series of steps of re-slurrying, elimination of aggregation, filtration, and dehydration of the precursor particles is repeated three times (washing three times) to obtain precursor particles containing a hydrophobic solvent.
[0380] (5) Solvent Removal Process
[0381] The precursor particles obtained in the above-mentioned washing step were dried at 40° C. using a dryer to perform preliminary drying.
[0382] Next, the precursor particles were heat-treated in a vacuum dryer at 200° C. for 12 hours to remove the hydrophobic solvent contained in the particles, thereby obtaining hollow particles of Example 1.
[0383] [Example 2]
[0384] In Example 1, hollow particles of Example 2 were produced by the same procedure as in Example 1, except that the number of washing times in the above-mentioned "(4) Washing Step" was changed from three times to four times.
[0385] [Examples 3 to 5]
[0386] In Example 1, in the above-mentioned "(1) mixed liquid preparation step", the type and amount of the polymerizable monomer added to the oil phase are changed according to Table 1, and in the above-mentioned "(4) cleaning step", the number of cleaning times is changed from three times to four times. Except for this, the hollow particles of Examples 3 to 5 are manufactured by the same steps as in Example 1.
[0387] [Comparative Example 1]
[0388] In Example 1, in the above-mentioned "(4) cleaning step", the precursor composition obtained in the polymerization step is treated only with dilute sulfuric acid (25°C, 10 minutes) to adjust the pH to below 5.5, and then the precursor particles are separated by filtration and dehydrated. Except for this, the hollow particles of Comparative Example 1 are manufactured by the same steps as in Example 1.
[0389] [Comparative Example 2]
[0390] In Example 1, hollow particles of Comparative Example 2 were produced by the same procedure as in Example 1, except that the number of washing times was changed from three times to one time in the above-mentioned "(4) Washing Step".
[0391] [Comparative Example 3]
[0392] In Example 1, hollow particles of Comparative Example 3 were produced by the same procedure as in Example 1, except that the number of washing times in the above-mentioned "(4) Washing Step" was changed from three times to two times.
[0393] [Comparative Example 4]
[0394] In Example 1, when preparing the aqueous phase in the above-mentioned "(1) mixed solution preparation step", 0.313 parts of anionic surfactant was added to the magnesium chloride aqueous solution, and further, in the above-mentioned "(4) washing step", the number of washing times was changed from three times to two times. Except for this, the hollow particles of Comparative Example 4 were manufactured by the same steps as in Example 1.
[0395] [Comparative Example 5]
[0396] Hollow particles of Comparative Example 5 were produced in the same manner as in Production Example 1 of Patent Document 1 (Japanese Patent Application Laid-Open No. 2000-313818).
[0397] That is, an aqueous solution obtained by dissolving 0.5 parts of a reactive emulsifier SE10N (manufactured by Aidico Co., Ltd.) and 1.0 parts of ammonium persulfate in 200 parts of distilled water is polymerized at 75°C for 8 hours while stirring with 70 parts of styrene, 27 parts of butadiene, 3 parts of itaconic acid, and 12 parts of tert-dodecyl mercaptan to obtain polymer particles. Next, the polymer particles are used as seed polymers and the following polymerization is performed. That is, 10 parts of the polymer particles, 0.1 parts of polyoxyethylene nonylphenyl ether and 0.4 parts of ammonium lauryl sulfate as surfactants, and 0.5 parts of ammonium persulfate are dispersed in 900 parts of distilled water. A mixture of 50 parts of methyl methacrylate, 40 parts of divinylbenzene, 10 parts of α-methylstyrene and 20 parts of toluene is added thereto, and the mixture is polymerized at 75°C for 5 hours, resulting in a dispersion of precursor particles containing toluene inside the particles. The obtained precursor particles were spray-dried to obtain hollow particles of Comparative Example 5.
[0398] [Comparative Example 6]
[0399] As hollow particles corresponding to Patent Document 3 (International Publication No. 2021 / 085189), hollow particles of Comparative Example 6 were produced.
[0400] First, the following materials were mixed to prepare an oil phase.
[0401] Styrene 12.5 parts
[0402] 16.2 parts of divinylbenzene
[0403] 3.8 parts of ethylvinylbenzene
[0404] HS CRYSTA 4100 (: product name, side chain crystalline polyolefin, manufactured by Toyokuni Oil Manufacturing Co., Ltd.) 3.3 parts
[0405] Blemmer (registered trademark) 50PEP-300 (product name, polyethylene glycol propylene glycol monomethacrylate, manufactured by NOF Corporation) 3.3 parts
[0406] Peroyl L (product name, polymerization initiator, manufactured by NOF Corporation) 1.07 parts
[0407] Hydrophobic solvent: 26.04 parts of heptane
[0408] Next, 370 parts of ion-exchanged water and 0.18 parts of RAPISOL A-80 (surfactant, manufactured by NOF Corporation) were mixed to prepare an aqueous phase.
[0409] The oil phase was added to the aqueous phase, and a suspension was prepared using an ultrasonic homogenizer. The obtained suspension was heated at 70° C. for 4 hours to polymerize and obtain a slurry. The obtained slurry was heated at 100° C. for 24 hours to obtain hollow particles of Comparative Example 6.
[0410] [Comparative Example 7]
[0411] In Example 1, in the above-mentioned "(1) mixed liquid preparation step", the type and amount of the polymerizable monomer and the hydrophobic solvent added to the oil phase are changed according to Table 1, in the above-mentioned "(3) polymerization step", the polymerization temperature is changed to 40°C, and the polymerization time is changed to 4 hours. In the above-mentioned "(4) cleaning step", no non-ionic surfactant for eliminating the agglomeration of the precursor particles is added to the slurry after pH adjustment and the slurry after re-slurry. Except for this, the hollow particles of Comparative Example 7 are manufactured by the same steps as in Example 1.
[0412] [evaluate]
[0413] The following measurements and evaluations were performed on the hollow particles obtained in the above-mentioned Examples and Comparative Examples.
[0414] 1. Volume average particle size (Dv)
[0415] The volume average particle size (Dv) of the hollow particles was measured using a particle size distribution analyzer using the Coulter counter method (Beckman Coulter, product name: Multisizer 4e). The measurement conditions were pore size: 50 μm, dispersion medium: ISOTON II (: product name), concentration: 10%, and number of particles measured: 100,000.
[0416] Specifically, 0.2 g of a particle sample was taken into a beaker, and a surfactant aqueous solution (manufactured by Fujifilm Corporation, product name: DRIWEL) was added thereto as a dispersant. 2 ml of a dispersion medium was further added thereto to wet the particles, and then 10 ml of a dispersion medium was added thereto, and the particles were dispersed for 1 minute using an ultrasonic disperser, and then measured using the above-mentioned particle size distribution measuring machine.
[0417] 2. Porosity
[0418] 2-1. Determination of apparent density of hollow particles
[0419] First, in the capacity of 100cm 3 Fill the volumetric flask to about 30 cm 3 The mass of the hollow particles is accurately weighed. Next, the volumetric flask filled with the hollow particles is filled to the mark with isopropyl alcohol while being careful not to allow air bubbles to enter. The mass of isopropyl alcohol added to the volumetric flask is accurately weighed, and the apparent density D1 (g / cm 3 ).
[0420] .
[0421] 2-2. Determination of true density of hollow particles
[0422] After the hollow particles are crushed in advance, the volume is 100cm 3 A volumetric flask is filled with about 10 g of hollow particle fragments, and the mass of the filled fragments is accurately weighed.
[0423] Then, isopropyl alcohol was added to the volumetric flask in the same manner as in the above-mentioned measurement of the apparent density, and the mass of the isopropyl alcohol was accurately weighed. The true density D0 (g / cm 3 ).
[0424] .
[0425] 2-3. Calculation of porosity
[0426] The porosity of the hollow particles is calculated based on the following formula (III) from the apparent density D1 and the true density D0 of the hollow particles.
[0427] .
[0428] 3. Residual monomer content
[0429] In the measurement of the residual monomer amount, in each of the Examples and Comparative Examples, hollow particles (precursor particles enclosing a hydrophobic solvent) after the washing step were prepared as measurement samples. The residual monomer amount in each measurement sample was measured by the following method.
[0430] Collect 3g of the solid content of the hollow particles and accurately weigh them to 1mg units. Add 27g of ethyl acetate and stir for 15 minutes, then add 13g of methanol and stir for further 10 minutes. Let the obtained solution stand to precipitate the insoluble components, and collect the supernatant of the solution as a sample for determination. Inject the sample for determination into a gas chromatograph, and quantify the amount of unreacted polymerizable monomers in the sample by gas chromatography (GC) under the following conditions. Calculate the proportion of unreacted polymerizable monomers contained in the solid content of the hollow particles as the residual monomer amount.
[0431] (Analysis conditions)
[0432] Equipment: GC-2010 (manufactured by Shimadzu Corporation)
[0433] Chromatographic column: DB-5 (manufactured by Agilent Technologies, Inc.)
[0434] Film thickness 0.25μm, inner diameter 0.25mm, length 30m
[0435] Detector: FID
[0436] Carrier gas: nitrogen (linear velocity: 28.8 cm / sec)
[0437] Inlet temperature: 200℃
[0438] Detector temperature: 250°C
[0439] Oven temperature: Increase from 40°C to 230°C at a rate of 10°C / min, and maintain at 230°C for 2 minutes
[0440] Sampling volume: 2μL
[0441] 4. pH and conductivity of hollow particle aqueous dispersion
[0442] To 100 mL of an aqueous solution (conductivity 1 μS / cm or less) in which a nonionic surfactant (product name: SN DEFOAMER 180, manufactured by San Nopco, Ltd., polyether-based) was dissolved at a concentration of 0.1% by mass in ion exchange water, a 0.35-cm volume of ethanol was added. 3 The hollow particles were stirred at 300 rpm for 3 hours at room temperature (25°C) to obtain an aqueous dispersion of the hollow particles. The pH and conductivity of the obtained aqueous dispersion of the hollow particles were measured. In addition, the obtained aqueous dispersion of the hollow particles was in a state where no powder existed in the upper part and all the powder was dispersed in the water when observed with the naked eye. In addition, as a volume of 0.35 cm 3 As the hollow particles, the hollow particles whose weight (g) was measured and calculated by the following formula (1) were used.
[0443] .
[0444] 5. Surfactant content on particle surface
[0445] 50 ml of ultrapure water and 5 g of hollow particles were accurately weighed and mixed thoroughly. Ultrasonic waves were irradiated for 30 minutes and filtered through a needle membrane filter with a diameter of 0.45 μm. The filtrate was freeze-dried, and 1 g of tetramethylsilane (TMS) solvent was added to the residue to dissolve it. The mixture was then subjected to the following conditions: 1 H-NMR measurement. 1 The surfactant determined by H-NMR spectrum is used to make a standard curve of TMS intensity benchmark to calculate the extraction amount of the surfactant extracted from the hollow particle surface. In addition, a standard curve is made according to the TMS intensity and the peak intensity ratio from the surfactant. The ratio of the extraction amount of the surfactant extracted from the hollow particle surface relative to the mass of the hollow particle is calculated as the content of the surfactant present on the hollow particle surface.
[0446] In addition, for 1 The H-NMR spectrum did not detect surfactant particles and was judged as not detected (ND).
[0447] < 1 H-NMR measurement conditions>
[0448] Device name: FT-NMR device
[0449] Resonance frequency: 400MHz
[0450] Measurement mode: 1H-NMR
[0451] Pulse width: 5.0μs (pulse angle: 90°)
[0452] Measurement range: 26ppm (frequency range: 10500Hz)
[0453] Total times: 1024 times
[0454] Measurement temperature: 40℃
[0455] Solvent: Deuterated chloroform (TMS (tetramethylsilane) 1%)
[0456] Reference substance: Peak derived from tetramethylsilane: 0.00 ppm (internal standard method)
[0457] 6. Metal content in particles
[0458] A microwave digester (Perkin Elmer, Multiwave 3000) was used to wet digest 10 g of hollow particles accurately weighed, and the digestate obtained was subjected to ICP emission analysis using an ICP emission analyzer (Perkin Elmer, Optima 2100DV) to determine the total mass of the metal. In addition, the metal species were determined by elemental analysis using fluorescent X-ray analysis (XRF). The ratio of the total mass of the metal in the digestate to the mass of the hollow particles was calculated as the metal content in the hollow particles.
[0459] 7. Relative dielectric constant (Dk) and dielectric loss tangent (Df)
[0460] The relative dielectric constant and dielectric loss tangent of the hollow particles were measured at a frequency of 10 GHz and room temperature (25° C.) using a perturbation type measuring device (manufactured by AET, model: ADMS01Nc).
[0461] 8. Porosity maintenance rate in the molded body
[0462] 90 parts of polypropylene (made by Japan Polypropylene Co., Ltd. (NOVATEC PP MA1B)) and 10 parts of hollow particles were mixed with a stirrer. Next, the obtained mixture was added to a metal mold, heated at 230°C, taken out after the polypropylene was dissolved, and 15MPa (surface pressure) was applied by a press after cooling to 130°C to make a molded body. Then, according to the specific gravity of the obtained molded body and the specific gravity of the hollow particles, the pore maintenance rate (%) of the hollow particles was calculated. The higher the pore maintenance rate of the hollow particles, the better the pressure resistance can be evaluated.
[0463] 9. Reliability test in high humidity environment
[0464] 9-1. Preparation of hollow particle-containing resin varnish
[0465] First, 90 parts of a brominated epoxy resin (manufactured by Tohto Kasei Co., Ltd., product name: YDB-500EK 75, epoxy equivalent 500, solid content 75% by mass) and 10 parts of a cresol novolac type epoxy resin (manufactured by Tohto Kasei Co., Ltd., product name: YDCN220EK 75, epoxy equivalent 210, solid content 75% by mass) were dissolved in a mixed solvent (room temperature) of 20 parts of dimethylformamide (DMF) and 6 parts of methyl ethyl ketone (MEK), and then 2 parts of dicyandiamide (DICY) (manufactured by Nippon Carbide Industries, Ltd.) and 0.1 parts of 2-ethyl-4-methylimidazole (product name: CUREZOL (registered trademark) 2E4MZ, manufactured by Shikoku Chemical Industries, Ltd.) were added, and the mixture was stirred and mixed to prepare a resin varnish.
[0466] Next, 95 parts of the resin varnish cooled to room temperature and 5 parts of the hollow particles were stirred and mixed at 3000 rpm for 30 minutes using a disperser, thereby obtaining a hollow particle-containing resin varnish.
[0467] 9-2. Preparation of prepreg
[0468] The obtained hollow particle-containing resin varnish was impregnated into glass cloth (manufactured by Nitto Bosho Co., Ltd., product name: WEA116E), and then heated and dried at 150 to 170° C. for 3 to 10 minutes to remove the solvent, thereby obtaining a prepreg.
[0469] 9-3. Production of double-sided copper-clad laminate
[0470] A 35 μm thick copper foil was placed on both sides of the obtained prepreg and heated at 180°C for 2 hours at a pressure of 2.94 MPa (30 kg / cm 2 ) under curing conditions to obtain a double-sided copper-clad laminate with a thickness of 0.13 mm.
[0471] 9-4. Reliability test
[0472] The obtained double-sided copper-clad laminate was subjected to high pressure cooking (110°C, humidity 85% RH, 100 hours of treatment). A voltage of 50V was applied to the treated double-sided copper-clad laminate for a specified time, and the resistance value was measured to confirm whether there was any abnormality, and the evaluation was performed according to the following evaluation criteria. In addition, the situation where the resistance value changed was judged to be abnormal. It can be considered that the change in resistance value is caused by the corrosion of the copper substrate.
[0473] (Reliability test evaluation criteria)
[0474] A: No abnormality even after voltage was applied for 400 hours
[0475] B: There is no abnormality even after the voltage is applied for 300 hours, but an abnormality occurs before the voltage is applied for 400 hours
[0476] C: There is no abnormality even after the voltage is applied for 200 hours, but an abnormality occurs before the voltage is applied for 300 hours
[0477] D: There is no abnormality even after the voltage is applied for 100 hours, but an abnormality occurs before the voltage is applied for 200 hours
[0478] E: Abnormality occurs before the voltage is applied for 100 hours
[0479] [Table 1]
[0480] .
[0481] Table 1 shows the amount (parts by mass) of each material added and the results of each measurement or evaluation.
[0482] In Table 1, for simplicity, the dielectric loss tangent values are expressed using indices specified in JIS X0210. For example, “8.44×10 -4 ” is expressed as “8.44E-04”.
[0483] In addition, the meanings of the abbreviations in Table 1 are as follows.
[0484] DVB: divinylbenzene
[0485] EVB: Ethyl Vinyl Benzene
[0486] St:Styrene
[0487] MMA: Methyl Methacrylate
[0488] α-MSt: α-methylstyrene
[0489] 50PEP-300: Polyethylene glycol propylene glycol monomethacrylate (manufactured by NOF Corporation, product name: Blemmer (registered trademark) 50PEP-300)
[0490] In addition, for the hollow particles obtained in each embodiment and each comparative example, SEM observation of the particle surface and particle cross section was performed. According to the SEM observation results and the porosity value, it can be confirmed that the hollow particles obtained in each embodiment and each comparative example except Comparative Example 6 are spherical and have only one hollow part. The hollow particles obtained in Comparative Example 6 were broken or dented. The number ratio of particles having only one hollow part in any embodiment is 90% or more.
[0491] Furthermore, as for the hollow particles obtained in each example, 3000 arbitrary particles were examined. As a result, in any example, the proportion of particles having a circularity of 0.85 or less was 10 mass % or less.
[0492] [Investigation]
[0493] The hollow particles obtained in Comparative Examples 1 to 7 were 3 The hollow particles of the present invention are dispersed in 100 mL of ion exchange water to obtain an aqueous dispersion of hollow particles having a pH greater than 7.5 and a conductivity greater than 50 μS / cm. Therefore, compared with the hollow particles obtained in each embodiment, the dielectric loss tangent is large, and abnormalities are easily caused in reliability tests, that is, the performance stability under high humidity environments is poor. In addition, the hollow particles obtained in Comparative Examples 5 to 6 have poor pressure resistance because the content of the cross-linked monomer unit is less than 60% by mass. The hollow particles obtained in Comparative Example 7 have poor pressure resistance because the amount of residual monomers is large.
[0494] In contrast, the hollow particles obtained in each example have a volume of 0.35 cm 3 The hollow particles are dispersed in 100mL of ion exchange water to obtain the aqueous dispersion of hollow particles with a pH of more than 6.5 and less than 7.5, and a conductivity of less than 50 μS / cm, so the dielectric loss tangent is small, and it is not easy to be abnormal in the reliability test, that is, the performance stability under high humidity is excellent. In addition, the hollow particles obtained in each embodiment have an excellent pressure resistance because the content of the crosslinking monomer unit in all monomer units of 100% by mass of the polymer contained in the shell is more than 60% by mass, and the porosity can be increased to more than 50%. It is speculated that the porosity is sufficiently high, which is also one of the reasons why the dielectric loss tangent of the hollow particles obtained in each embodiment is small. In addition, it is speculated that the high content of hydrocarbon monomer units is also one of the reasons why the dielectric loss tangent of the hollow particles obtained in each embodiment is low. The hollow particles obtained in Examples 3 to 5 contain a combination of crosslinkable hydrocarbon monomer units and non-crosslinkable hydrocarbon monomer units and increase the proportion of non-crosslinkable hydrocarbon monomer units. Therefore, compared with the hollow particles obtained in Examples 1 to 2, the dielectric loss tangent is further reduced and the dielectric properties are particularly excellent.
[0495] [Example 6]
[0496] (1) Preparation of resin composition
[0497] The same hollow particle-containing resin varnish prepared in "9-1. Preparation of hollow particle-containing resin varnish" of "9. Reliability test under high humidity environment" of Example 2 was used as the resin composition of Example 6. The addition amount of each material was adjusted so that the total solid content contained in the resin composition was 100 parts by mass.
[0498] That is, first, 90 parts of brominated epoxy resin (manufactured by Tohto Kasei Co., Ltd., product name: YDB-500EK 75, epoxy equivalent 500, solid content 75% by mass) and 10 parts of cresol novolac type epoxy resin (manufactured by Tohto Kasei Co., Ltd., product name: YDCN220EK 75, epoxy equivalent 210, solid content 75% by mass) are dissolved as a base resin in a mixed solvent (room temperature) of 20 parts of dimethylformamide (DMF) and 6 parts of methyl ethyl ketone (MEK), and then 2 parts of dicyandiamide (DICY) (manufactured by Nippon Carbide Industries, Ltd.) as a curing agent and 0.1 parts of 2-ethyl-4-methylimidazole (product name: CUREZOL (registered trademark) 2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.) as a curing accelerator are added, and the mixture is stirred and mixed to prepare a resin varnish.
[0499] Next, 118 parts (94 parts of solid content) of the resin varnish cooled to room temperature and 6 parts of the hollow particles prepared in Example 2 were stirred and mixed at 3000 rpm for 30 minutes using a disperser to prepare a resin composition of Example 6. The contents (parts by mass) of the components contained in the obtained resin composition are shown in Table 2.
[0500] (2) Preparation of resin molded body (cured product)
[0501] The obtained resin composition was filled into an aluminum metal mold frame covered with a Teflon (registered trademark) sheet, and then heated and cured at 180° C. for 3 hours in an oven under a nitrogen atmosphere to produce a sheet-like resin molded body which is a cured product of the resin composition obtained above.
[0502] [Example 7]
[0503] In Example 6, except that the amount of resin varnish added was changed to 122.5 parts (98 parts of solid content) and the amount of hollow particles added was changed to 2 parts, the resin composition of Example 7 and the resin molded body as its cured product were prepared by the same steps as in Example 6.
[0504] [Example 8]
[0505] In Example 6, except that the amount of resin varnish added was changed to 106.5 parts (solid content 85 parts) and the amount of hollow particles added was changed to 15 parts, the same steps as in Example 6 were followed to prepare the resin composition of Example 8 and the resin molded body as its cured product.
[0506] [Example 9]
[0507] (1) Preparation of Sealing Resin Composition
[0508] 48.8 parts of alicyclic epoxy resin (product name: CELLOXIDE 2021P, manufactured by Daicel Corporation) as a base resin, 44.3 parts of methylhexahydrophthalic anhydride (product name: RIKACID (registered trademark) MH, manufactured by Shin Nippon Rika Co., Ltd.) as an acid anhydride curing agent, and 0.89 parts of 1-benzyl-2-methylimidazole (product name: CUREZOL (registered trademark) 1B2MZ, manufactured by Shikoku Chemical Industry Co., Ltd.) as a curing accelerator were mixed and stirred for 15 minutes using a planetary mixer. The resulting mixture was cooled to room temperature, and then 6 parts of the hollow particles prepared in Example 2 were added to the mixture, and mixed and stirred at 3000 rpm for 30 minutes using a disperser to prepare a sealing resin composition of Example 9.
[0509] (2) Preparation of solidified material
[0510] The obtained sealing resin composition was filled into an aluminum metal mold frame covered with a Teflon (registered trademark) sheet and then heat-cured in an oven at 180° C. for 3 hours under a nitrogen atmosphere to prepare a sheet-like cured product of the sealing resin composition.
[0511] [Examples 10 to 15]
[0512] In Example 9, except for changing the type and addition amount of the base resin, the addition amount of the acid anhydride curing agent (RIKACID (registered trademark) MH), or the addition amount of the curing accelerator (1B2MZ) according to Table 2, the sealing resin compositions and their cured products of Examples 10 to 15 were prepared by the same steps as in Example 9.
[0513] [Comparative Example 8]
[0514] In Example 9, the hollow particles prepared in Comparative Example 2 were used instead of the hollow particles prepared in Example 2, and the type and addition amount of the base resin, the addition amount of the anhydride curing agent (RIKACID (registered trademark) MH), and the addition amount of the curing accelerator (1B2MZ) were changed according to Table 2. Otherwise, the sealing resin composition and its cured product of Comparative Example 8 were prepared by the same steps as in Example 9.
[0515] [evaluate]
[0516] The following measurements and evaluations were performed on the resin compositions and cured products obtained in Examples 6 to 15 and Comparative Example 8. The results are shown in Table 2.
[0517] 10. Porosity maintenance rate
[0518] From the specific gravity of the cured products obtained in Examples 6 to 15 and Comparative Example 8 and the specific gravity of the hollow particles added to each cured product, the porosity maintenance rate (%) of the hollow particles in the cured product was calculated.
[0519] 11. Reduction rate of dielectric loss tangent
[0520] Small pieces with a width of 2.6 mm, a length of 80 mm, and a thickness of 40 μm were cut out from the cured products obtained in Examples 6 to 15 and Comparative Example 8 to serve as measurement samples. The dielectric loss tangent of the measurement samples was measured at a frequency of 10 GHz and room temperature (25° C.) using a cavity resonator perturbation type dielectric constant dielectric loss tangent measuring apparatus.
[0521] On the other hand, a cured product not containing hollow particles was prepared by the same procedure as in Examples 6 to 15 and Comparative Example 8, except that the hollow particles were not added. The dielectric loss tangent was measured in the same manner as above for the cured product not containing hollow particles.
[0522] The reduction rate of the dielectric loss tangent of the hollow particle-containing cured products obtained in Examples 6 to 15 and Comparative Example 8 was calculated by the following formula and evaluated according to the following evaluation criteria.
[0523] In the following formula, the dielectric loss tangent of the cured product containing hollow particles is referred to as Df1, and the dielectric loss tangent of the cured product produced under the same conditions except that the hollow particles are not contained is referred to as Df2.
[0524] .
[0525] (Evaluation Criteria)
[0526] A: The reduction rate of dielectric loss tangent is more than 12%
[0527] B: The reduction rate of dielectric loss tangent is more than 6% and less than 12%
[0528] C: The reduction rate of dielectric loss tangent is less than 6%
[0529] 12. Reliability test in high humidity environment
[0530] Using the resin compositions obtained in Examples 6 to 15 and Comparative Example 8, prepregs were obtained by the same procedure as in "9-2. Preparation of prepreg" in the above "9. Reliability test under high humidity environment".
[0531] The obtained prepreg was used to obtain a double-sided copper-clad laminate by the same procedure as in "9-3. Preparation of double-sided copper-clad laminate" in the above "9. Reliability test under high humidity environment" to obtain a double-sided copper-clad laminate.
[0532] The obtained double-sided copper-clad laminate was used to perform evaluation according to the same procedure and evaluation criteria as those in "9-4. Reliability test" of the above-mentioned "9. Reliability test under high humidity environment".
[0533] [Table 2]
[0534] .
[0535] The meanings of the abbreviations in Table 2 are as follows.
[0536] YDB-500EK 75: Product name "YDB-500EK 75", manufactured by Tohto Kasei Co., Ltd., brominated epoxy resin
[0537] YDCN220EK 75: Product name "YDCN220EK 75", manufactured by Tohto Kasei Co., Ltd., cresol novolac type epoxy resin
[0538] CEL2021P: Product name "CELLOXIDE 2021P", manufactured by Daicel Corporation, a compound represented by the following formula (B)
[0539] EHPE3150: product name "EHPE 3150", manufactured by Daicel Corporation, a compound represented by the following formula (C)
[0540] CEL2081: Product name "CELLOXIDE 2081", manufactured by Daicel Corporation, a compound represented by the following formula (D)
[0541] GT401: Product name "EPOLEAD GT401", manufactured by Daicel Corporation, a compound represented by the following formula (E)
[0542] THI-DE: Product name "EPOCHALIC (registered trademark) THI-DE", manufactured by ENES Co., Ltd., a compound represented by the following formula (F)
[0543] jER828EL: Product name "jER828EL", manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy compound, epoxy equivalent 189
[0544] NC-3000-L: Product name "NC-3000-L", manufactured by Nippon Kayaku Co., Ltd., biphenyl aralkyl type epoxy compound, epoxy equivalent 269
[0545] 2E4MZ: Product name "CUREZOL (registered trademark) 2E4MZ", manufactured by Shikoku Chemical Industry Co., Ltd., 2-ethyl-4-methylimidazole
[0546] 1B2MZ: Product name "CUREZOL (registered trademark) 1B2MZ", manufactured by Shikoku Chemical Industry Co., Ltd., 1-benzyl-2-methylimidazole
[0547] DICY: Dicyandiamide, manufactured by Nippon Carbide Industries, Ltd.
[0548] RIKACID MH: Product name "RIKACID MH", manufactured by Shin Nippon Rika Co., Ltd., methylhexahydrophthalic anhydride
[0549] [Chemical formula 2]
[0550] .
[0551] n in the above formula (C) and n in the above formula (D) are each an integer greater than or equal to 1, and n1, n2, n3 and n4 in the above formula (E) are each an integer greater than or equal to 0.
[0552] [Investigation]
[0553] The resin composition obtained in Comparative Example 8 and the resin molded body as its cured product include the hollow particles of Comparative Example 2. Since the hollow particles of Comparative Example 2 have a pH greater than 7.5 and a conductivity greater than 50 μS / cm in their aqueous dispersion, the resin composition obtained in Comparative Example 8 and the resin molded body as its cured product are prone to abnormalities in reliability tests, that is, poor performance stability under high humidity environments. In addition, in Comparative Example 8, the reduction rate of the dielectric loss tangent is smaller than that of the embodiment to which the same amount of hollow particles is added, and the reduction effect of the dielectric loss tangent brought by the hollow particles is also poor.
[0554] In contrast, the resin composition obtained in Examples 6 to 15 and the resin molded body as its cured product include the hollow particles of Example 2. The hollow particles of Example 2 have a pH of more than 6.5 and less than 7.5 in its aqueous dispersion and a conductivity of less than 50 μS / cm, so the resin composition obtained in Examples 6 to 15 and the resin molded body as its cured product have a large reduction rate of dielectric loss tangent brought by hollow particles, and are not prone to abnormality in reliability tests, that is, excellent performance stability under high humidity environments. Therefore, this shows that the resin composition and resin molded body of the present invention comprising the hollow particles of the present invention and the matrix resin suppress the reduction of performance stability under high humidity environments by containing hollow particles while reducing the dielectric loss tangent.
[0555] Description of Reference Numerals
[0556] 1: Water-based medium;
[0557] 1a: ion exchange water;
[0558] 2: Low polarity materials;
[0559] 3: droplets of monomer composition;
[0560] 4a: hydrophobic solvent;
[0561] 4b: Materials other than hydrophobic solvents;
[0562] 5: Precursor particles;
[0563] 6: Shell;
[0564] 7: hollow part;
[0565] 10: Hollow particles whose hollow parts are filled with gas.
Claims
1. A hollow particle having a shell containing a resin and a hollow portion surrounded by the shell, The porosity of the hollow particles is greater than 50%. The shell contains a polymer as the resin, and the content of crosslinkable monomer units is 60% by mass or more in 100% by mass of all monomer units of the polymer. When the volume is 0.35cm 3 In an aqueous dispersion of hollow particles obtained by dispersing the hollow particles of in 100 mL of ion-exchanged water, the pH is 6.5 to 7.5, and the electrical conductivity is 50 μS / cm or less.
2. The hollow particles according to claim 1, wherein The content of hydrocarbon monomer units in 100% by mass of all monomer units of the polymer is greater than 50% by mass.
3. The hollow particles according to claim 1 or 2, wherein The content of the metal in the hollow particles is 700 ppm or less.
4. The hollow particles according to claim 1 or 2, wherein The content of the surfactant present on the surface of the hollow particles is 200 ppm or less.
5. The hollow particles according to claim 1 or 2, wherein The dielectric loss tangent of the hollow particles at a frequency of 10 GHz is 1.00×10 -3 the following.
6. The hollow particles according to claim 1 or 2, wherein The hollow particles have a relative dielectric constant of 1.00 or more and 1.40 or less at a frequency of 10 GHz.
7. The hollow particles according to claim 1 or 2, wherein The porosity is greater than 70%. 8 . A resin composition comprising a matrix resin and the hollow particles according to claim 1 . 9 . A resin molded product obtained from the resin composition according to claim 8 . 10 . A sealing resin composition comprising an epoxy resin and the hollow particles according to claim 1 .
11. The sealing resin composition according to claim 10, wherein The sealing resin composition includes an alicyclic epoxy resin as the epoxy resin.
12. The sealing resin composition according to claim 11, wherein The sealing resin composition further includes an epoxy resin having no alicyclic structure as the epoxy resin.
13. The sealing resin composition according to claim 10, wherein The sealing resin composition further includes a curing accelerator.
14. The sealing resin composition according to claim 10, wherein The content of the hollow particles is 1 to 70 parts by mass based on 100 parts by mass of the total solid content contained in the sealing resin composition. 15 . A cured product, which is a cured product of the sealing resin composition according to claim 10 . 16 . A semiconductor device comprising the cured product according to claim 15 as a sealing material.
Citation Information
Patent Citations
Crosslinked resin particle, composition for organic insulation material, organic insulation material, sealant and circuit board
JP2000313818A
Thermally expansive microspheres, and production method and use of the same
JP2015003951A
Hollow resin particle and method for producing same
WO2021085189A1
Method for prducing hollow particles, and hollow particles
WO2022092076A1